Abrasive particles including coating, abrasive articles including abrasive particles, and methods of forming
By coating the core of abrasive particles with a specific ratio of lithium, potassium, sodium, and silicon compounds, the problem of poor performance of organically bonded abrasive products under wet grinding conditions is solved, thereby improving the performance and service life of the abrasive products.
Patent Information
- Application Number
- CN202310743048.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
Existing organically bonded abrasive products perform poorly under wet grinding conditions, and there is a need to improve the performance of abrasive products and the bonding between the binder and the abrasive particles.
A coating is applied to the core, containing a compound of lithium, potassium, sodium and silicon in a specific ratio, such as a lithium/silicon percentage between 0.01% and 25%, to promote improved coating formation and properties, and to form improved coating thickness and abrasive particle morphology through a drying process.
It improves the performance of abrasive particles under wet grinding conditions, enhances the bonding between the binder and the abrasive particles, and improves the performance and service life of the grinding products.
Smart Images

Figure CN119177112A_ABST
Abstract
Description
Technical Field
[0001] The following relates to abrasive grains including a coating covering a portion of a core, abrasive articles including the abrasive grains, and methods of formation. Background Art
[0002] Abrasive articles are used in material removal operations, such as cutting, grinding or shaping various materials. Fixed abrasive articles include abrasive particles held in a bonding material. The bonding material may include organic and / or inorganic materials. Organic bonded abrasive articles generally do not perform well under wet grinding conditions. Specifically, in wet grinding operations. The industry continues to demand improved abrasive articles. Summary of the invention
[0003] The present application provides an abrasive particle, comprising: a main body, wherein the main body includes: a core, and a coating, wherein the coating covers at least a portion of the core, wherein the coating comprises at least one of the following: a) a lithium / silicon percentage in the range of at least 0.01% to not more than 25%; b) a potassium / silicon percentage in the range of at least 0.01% to not more than 40%; c) a sodium / silicon percentage in the range of at least 0.01% to not more than 40%; or d) any combination thereof.
[0004] The present application also provides a fixed abrasive product comprising the abrasive particles.
[0005] The present application further provides an abrasive particle, comprising: a main body, the main body comprising: a core, and a coating, the coating covering at least a portion of the core, wherein the coating comprises a total crystal content of no more than 60 vol% of the total volume of the coating, wherein the coating comprises at least one silicate-containing compound and at least one silica-containing compound; and wherein the coating comprises a silicate / silicon dioxide percentage of at least 10% and no more than 1000%. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] The present disclosure may be better understood, and its numerous features and advantages made apparent to those skilled in the art by referencing the accompanying drawings.
[0007] Figure 1 A flow chart illustrating a process for forming abrasive particles according to one embodiment is included, wherein each abrasive particle may include a coating overlying a core.
[0008] Figure 2A and 2B Included is an illustration of a cross-section of an abrasive particle according to one embodiment.
[0009] Figure 3 Includes atomic force microscopy images of abrasive particles.
[0010] Figure 4 Included is an illustration of a cross-section of a bonded abrasive article according to one embodiment.
[0011] Figure 5 Included is an illustration of a process for forming an abrasive article according to one embodiment.
[0012] Figure 6 Included is an illustration of a cross-section of a coated abrasive article according to one embodiment.
[0013] Figure 7 Photos of Comparative Example 7 are included.
[0014] Fig. 8A and Figure 8B SEM images of cores comprising abrasive particles of the examples herein.
[0015] Fig. 9 Included is a plot of G-Ratio versus MRR for the grinding wheel samples.
[0016] FIG. 10A to FIG. 10H Included are SEM images of abrasive grain samples.
[0017] FIG. 11A to FIG. 11D SEM images of additional abrasive grain samples are included.
[0018] Those skilled in the art will appreciate that, for simplicity and clarity, the various elements shown in the figures are not necessarily drawn to scale. For example, the sizes of some elements in the figures may be enlarged relative to other elements to help enhance understanding of the embodiments of the present invention. DETAILED DESCRIPTION
[0019] The following description in conjunction with the accompanying drawings is provided to help understand the teachings provided herein. The following disclosure will focus on the specific implementation and embodiments of this teaching. This emphasis is provided to help describe the teachings and should not be interpreted as limiting the scope or applicability of this teaching. However, other teachings may certainly be used in this application.
[0020] As used herein, the terms "comprises," "including," "having," "having" or any other variation thereof are intended to cover a non-exclusive inclusion. For example, a method, article, or apparatus that includes a list of features is not necessarily limited to only those features, but may include other features not expressly listed or inherent to such method, article, or apparatus. In addition, unless expressly stated otherwise, "or" refers to an inclusive "or" rather than an exclusive "or." For example, any of the following may satisfy condition A or B: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist).
[0021] Furthermore, "a" or "an" is used to describe the elements and components described herein. This is done only for convenience and to give a general sense of the scope of the invention. Unless it is obvious that it is otherwise intended, this description should be understood to include one or at least one, and the singular also includes the plural, or vice versa. For example, when a single item is described herein, more than one item can be used in place of the single item. Similarly, where more than one item is described herein, a single item can replace more than one item.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs. The materials, methods, and examples are illustrative only and not limiting. To the extent that certain details regarding specific materials and processing methods are not described, such details may include conventional methods, which can be found in reference books and other sources in the field of manufacturing.
[0023] Embodiments relate to abrasive particles, wherein each abrasive particle may include a coating covering a core. The abrasive particles may include a batch of abrasive particles or otherwise have a suitable sample size of static correlation. The abrasive particles may be suitable for forming various abrasive articles, including, for example, fixed abrasive articles, such as bonded abrasive tools, coated abrasive tools, and superhard abrasive articles. The abrasive particles may have improved bonding with the bonding material contained in the abrasive article and promote improved performance of the abrasive article.
[0024] Embodiments also relate to a process for forming abrasive grains. The process may include a drying process to promote the formation of a coating with improved properties. For example, the process may allow the formation of abrasive grains with improved coating average thickness, improved coating thickness standard deviation, and improved abrasive grain morphology. In another example, the coating may promote the formation of improved moisture resistance and an interface of the abrasive grains, which has improved moisture resistance between the abrasive grains and the bonding material in the abrasive article.
[0025] Further embodiments relate to abrasive articles comprising a bonding material and abrasive particles. The abrasive article can have an improved bond between the bonding material and the abrasive particles, which in turn can help improve the performance and / or properties of the abrasive article. For example, the abrasive articles of embodiments herein can have improved grinding performance under wet conditions, improved performance after aging, and extended service life.
[0026] The abrasive article may include a fixed abrasive article, including, for example, coated abrasives (such as belts and discs), bonded abrasives (including organic bonding materials and / or inorganic bonding materials), and superhard abrasive tools. Exemplary bonded abrasive articles may include, for example, grinding wheels, cut-off wheels, ultra-thin wheels, combination wheels, cutting wheels, cut-off saws, or any combination thereof.
[0027] Figure 1 Included is a flow chart illustrating an exemplary process of forming abrasive particles, wherein each abrasive particle may include a coating covering a core. At frame 101, the process may include forming a coating. Forming a coating may include forming a mixture including a first material, a second material, and an optional third material. Suitable mixing operations may be utilized to achieve uniform dispersion of each component in the mixture.
[0028] The formation of the coating can include forming a mixture comprising a first material, the first material comprising silicon dioxide. For example, the first material can comprise a dispersion of silicon dioxide in a solvent. The solvent can be an aqueous solvent or an organic solvent. On the one hand, the first material can comprise silicon dioxide nanoparticles. In one embodiment, the first material can be a dispersion of silicon dioxide nanoparticles in water.
[0029] On the other hand, the coating may include a first material containing silicon (i.e., silicon dioxide) in a specific amount of the total weight of the mixture or the total weight of the first portion of the coating (e.g., 202), which may promote improved formation and properties of the coating. For example, the mixture and the resulting coating may include at least 10 wt.% of the first material containing silicon, such as at least 15 wt.%, at least 20 wt.%, at least 30 wt.%, at least 40 wt.%, at least 50 wt.%, at least 60 wt.%, at least 70 wt.%, or at least 80 wt.% of the total weight of the mixture. In another example, the mixture may include no more than 95 wt.% of the first material containing silicon, such as no more than 90 wt.%, or no more than 85 wt.% of the total weight of the mixture. It should be understood that the mixture may include a first material containing silicon in an amount including any minimum percentage and maximum percentage mentioned herein. Unless otherwise stated, the content of any substance (e.g., silicon, lithium, potassium, sodium, aluminum, etc.) is calculated by ICP analysis, as described in the measurement of abrasive particles in Example 1 (Sample S1) provided herein. As used herein, ICP can be performed using ICP-OES Agilent 5110 or equivalent. The microparticle sample can be prepared as follows: 0.5000±0.0100 grams of sample and 3.0000±0.0100 grams of lithium tetraborate are weighed and added to a Pt / Au crucible; 200 μl of lithium bromide solution is added to the crucible and mixed thoroughly; the mixture is melted at 1300±30°C, and then cooled to obtain a molten piece, which is then transferred to a beaker; approximately 125 mL of DI H2O and 25 mL of HCl are added to the beaker, and heated, and then cooled to obtain a solution for ICP testing.
[0030] The formation of the coating can include forming a mixture containing a second material, the second material containing lithium. For example, the second material can contain lithium silicate. In a particular embodiment, the coating can contain a second material containing lithium at a specific content of the total weight of the mixture, which can promote the improved formation and properties of the coating. For example, the mixture can contain at least 10wt.% of the second material containing lithium accounting for the total weight of the mixture, such as at least 15wt.%, at least 20wt.%, at least 30wt.%, at least 40wt.%, at least 50wt.%, at least 60wt.%, at least 70wt.%, or at least 80wt.%. In another example, the mixture can contain no more than 95wt.% of the second material containing lithium accounting for the total weight of the mixture, such as no more than 90wt.%, or no more than 85wt.% of the total weight of the mixture. It should be understood that the mixture can contain a second material containing lithium whose content includes any minimum percentage and maximum percentage mentioned herein.
[0031] In a non-limiting embodiment, the formation of the coating (e.g., the first part of the coating) can include forming a mixture containing an optional third material, the third material containing potassium. For example, the third material can include potassium silicate. In a specific embodiment, the coating can include a specific content of the third material accounting for the total weight of the mixture, which can promote the formation and properties of the coating. For example, the mixture can include at least 0.01wt% of the third material containing potassium accounting for the total weight of the mixture, such as accounting for at least 2wt.%, at least 4wt.%, at least 6wt.%, at least 8wt.%, at least 10wt.%, at least 15wt.%, at least 20wt.%, at least 25wt.%, at least 30wt.%, at least 35wt.%, at least 40wt.%, at least 45wt.%, or at least 50wt.%. In another example, the mixture can include no more than 70wt.% of the third material containing potassium accounting for the total weight of the mixture, such as accounting for no more than 65wt.%, no more than 60wt.%, or no more than 55wt.%. Additionally, the mixture can include a third material comprising potassium in an amount including any of the minimum percentages and maximum percentages mentioned herein.
[0032] In some other embodiments, the formation of the coating may include forming a mixture comprising an optional fourth material, which comprises sodium. For example, the fourth material may comprise sodium silicate. In a particular embodiment, the coating may include a specific content of the fourth material accounting for the total weight of the mixture, which may promote the formation and properties of the coating. For example, the mixture may include at least 0.01wt% of the fourth material comprising sodium accounting for the total weight of the mixture, such as at least 2wt.%, at least 4wt.%, at least 6wt.%, at least 8wt.%, at least 10wt.%, at least 15wt.%, at least 20wt.%, at least 25wt.%, at least 30wt.%, at least 35wt.%, at least 40wt.%, at least 45wt.%, or at least 50wt.%. In another example, the mixture may include no more than 70wt.% of the fourth material comprising sodium accounting for the total weight of the mixture, such as no more than 65wt.%, no more than 60wt.%, or no more than 55wt.%. Additionally, the mixture can include a fourth material comprising sodium in an amount including any of the minimum percentages and maximum percentages mentioned herein.
[0033] Now refer to box 102 or Figure 1, the process may further include applying a coating to at least a portion of the core. Applying the coating to at least a portion of the core may include mixing the core with the mixture formed in frame 101. A mixing device may be used to promote the formation of a uniform mixture of the core and the mixture. Examples of mixing devices may include a Hobart mixer, a Hudson mixer, etc., or other mixing devices.
[0034] exist Figure 1 In the next step of frame 103 of the present invention, the process may further include drying the core coated with the mixture. Drying may include drying at a temperature sufficient to form a coating covering at least a portion of the core. In particular, drying may be performed at a temperature of at least 15°C, or at least 20°C, or at least 30°C, or at least 40°C, or at least 50°C, such as at least 60°C, or at least 70°C, or at least 80°C, or at least 90°C, or at least 100°C, such as at least 120°C, or at least 150°C. In another example, the drying temperature may be no more than 400°C, such as no more than 350°C, no more than 300°C, no more than 250°C, no more than 200°C, such as no more than 190°C, no more than 180°C, no more than 170°C, or no more than 160°C. In addition, the drying temperature may be within the range of any minimum and maximum temperatures described herein. In a specific example, the drying temperature may be in the range of 100°C to 180°C, or in the range of 140°C to 150°C.
[0035] On the one hand, drying can be carried out in an oven.On the other hand, drying can be carried out for a period of time that is enough to form a dry coating on the core.For example, drying can include drying the core with coating for at least 2 hours, such as at least 4 hours, at least 6 hours, at least 8 hours, at least 10 hours, at least 12 hours or at least 14 hours.In another example, drying can be carried out for no more than 20 hours with the core with coating, such as no more than 18 hours or no more than 16 hours.In addition, drying can include drying the core with coating for a period of time in the scope of any minimum and maximum values mentioned herein.In a specific example, drying can include drying the core with coating for 12 hours to 16 hours.
[0036] It is noteworthy that the formation process disclosed in the embodiments herein can allow for improved formation of abrasive particles. For example, the dried abrasive particles can include 30 wt% of agglomerated abrasive particles accounting for the total weight of the dried abrasive particles, such as no more than 25 wt%, no more than 20 wt%, no more than 15 wt%, no more than 10 wt%, no more than 5 wt%, no more than 2 wt%, no more than 1 wt%, no more than 0.8 wt%, no more than 0.5 wt%, no more than 0.3 wt%, or no more than 0.1 wt% of agglomerated abrasive particles accounting for the total weight of the dried abrasive particles. In a specific example, the dried abrasive particles can be substantially composed of loose abrasive particles.
[0037] In one embodiment, the core may include an abrasive material including a crystalline material, such as a polycrystalline material, a single crystal material, or a combination thereof, an amorphous material, a ceramic material, a glass-ceramic material, a superabrasive, a mineral, a carbon-based material, or any combination thereof. In yet another aspect, the sintered ceramic material may include an oxide, a carbide, a nitride, a boride, an oxycarbide, an oxynitride, a silicate, or any combination thereof. For example, the core may include a material selected from the group consisting of silicon dioxide, silicon carbide, aluminum oxide, zirconium oxide, flint, garnet, corundum, rare earth oxides, rare earth-containing materials, cerium oxide, sol-gel particles, gypsum, iron oxide, glass-containing particles, and any combination thereof. In another example, the abrasive particles may also include silicon carbide (e.g., Green 39C and Black 37C), brown fused alumina (57A), seeded gel abrasive, sintered alumina containing additives, formed and sintered alumina, pink alumina, ruby alumina (e.g., 25A and 86A), fused single crystal alumina 32A, MA88, alumina-zirconia abrasive (e.g., NZ, NV and ZF brands from Saint-Gobain), extruded bauxite, sintered bauxite, cubic boron nitride, diamond, aluminum oxynitride, sintered alumina (e.g., CCCSK from Treibacher), extruded alumina (e.g., SR1, TG and TGII available from Saint-Gobain), or any combination thereof. In another example, the core may have a Mohs hardness of at least 7, such as at least 8, or even at least 9.
[0038] In another embodiment, the core may include non-agglomerated particles, non-shaped abrasive particles, shaped abrasive particles, or any combination thereof. For example, the core may include shaped abrasive particles, such as disclosed in US 20150291865, US20150291866, and US 20150291867. The shaped abrasive particles are formed so that for shaped abrasive particles with the same two-dimensional shape and three-dimensional shape, each particle has a substantially identical surface and edge arrangement relative to each other. Therefore, relative to other shaped abrasive particles of the group with the same two-dimensional shape and three-dimensional shape, the shaped abrasive particles can have high shape fidelity and stability in the surface and edge arrangement. On the contrary, non-shaped abrasive particles can be formed by different processes and have different shape attributes. For example, non-shaped abrasive particles are usually formed by a comminution process, in which a large amount of material is formed, then broken and sieved to obtain a certain size of abrasive particles. However, non-shaped abrasive particles will have a general random arrangement of surfaces and edges, and generally lack any recognizable two-dimensional shape or three-dimensional shape in the surface and edge arrangement around the body. In addition, the non-shaped abrasive particles of the same group or batch generally lack a consistent shape relative to each other, so that when compared to each other, the surfaces and edges are randomly arranged. Therefore, compared with shaped abrasive particles, non-shaped grains or broken grains have significantly lower shape fidelity.
[0039] In a particular embodiment, the core can include a sintered ceramic material having a particular average grain size. In one aspect, the average grain size can be less than 1 micron, such as no greater than 0.9 microns, no greater than 0.8 microns, no greater than 0.7 microns, no greater than 0.6 microns, no greater than 0.5 microns, no greater than 0.4 microns, no greater than 0.3 microns, no greater than 0.2 microns, no greater than 0.1 microns, no greater than 0.09 microns, no greater than 0.08 microns, no greater than 0.07 microns, no greater than 0.06 microns, no greater than 0.05 microns, no greater than 0.04 microns, no greater than 0.03 microns, no greater than 0.02 microns, or no greater than 0.01 microns. In another aspect, the core 201 may include a sintered ceramic material having an average grain size of at least 0.01 micrometers, such as at least 0.02 micrometers, at least 0.03 micrometers, at least 0.04 micrometers, at least 0.05 micrometers, at least 0.06 micrometers, at least 0.07 micrometers, at least 0.08 micrometers, at least 0.09 micrometers, at least 0.1 micrometers, at least 0.11 micrometers, at least 0.12 micrometers, at least 0.13 micrometers, at least 0.14 micrometers, at least 0.15 micrometers, at least 0.16 micrometers, at least 0.17 micrometers, at least 0.18 micrometers, at least 0.19 micrometers, at least 0.2 micrometers, at least 0.3 micrometers, at least 0.4 micrometers, or at least 0.5 micrometers. Further, the core may include a sintered ceramic material including an average grain size within a range including any minimum and maximum values noted herein. For example, the core may include a sintered ceramic material having an average grain size within the range of at least 0.01 micrometers and less than 1 micrometer, at least 0.03 micrometers and no more than 0.8 micrometers, at least 0.05 micrometers and no more than 0.6 micrometers, at least 0.08 micrometers and no more than 0.4 micrometers, or at least 0.1 micrometers and no more than 0.2 micrometers. The average grain size may be measured from SEM micrographs by an uncorrected intercept method.
[0040] A specific example of a sintered ceramic material may include alumina (Al2O3), including, for example, microcrystalline alumina (e.g., sol-gel alumina), nanocrystalline alumina, fused alumina, such as brown fused alumina, or a combination thereof. In particular, the alumina (Al2O3) may include alpha alumina (α-Al2O3).
[0041] In a particular aspect, the core can include polycrystalline alpha alumina (α-Al2O3), and more particularly, the polycrystalline alpha alumina (α-Al2O3) can include an average grain size of less than 1 micron, such as the average grain size described with respect to the sintered ceramic material. In an even more specific aspect, the core can consist essentially of polycrystalline alpha alumina (α-Al2O3) including an average grain size of less than 1 micron.
[0042] In one embodiment, the core may include a density of at least 80% of its theoretical density, such as at least 85%, at least 88%, at least 90%, at least 92%, at least 95%, or at least 98% of its theoretical density. In another embodiment, the core may include a porosity of no more than 10 vol% of the total volume of the core, such as no more than 9 vol%, no more than 8 vol%, no more than 7 vol%, no more than 6 vol%, no more than 5 vol%, no more than 4 vol%, no more than 3 vol%, no more than 2 vol%, or no more than 1 vol%. In a specific embodiment, the core may be substantially free of pores. The true density of the core is measured by first measuring the bulk density of the core. The bulk density of the core is measured by a specific gravity bottle (Quantachrome Ultrapycnometer 1000), in which ultra-high purity compressed helium is adjusted to a pressure of 20 psig. The core is then crushed into a powder state, and the true density is measured using a specific gravity bottle in the same manner as described above. The porosity of the core is calculated by the following calculation method (porosity=[true density-bulk density] / [true density]).
[0043] In yet another embodiment, the core may have a density of the sintered ceramic material forming the core. For example, depending on the sintered ceramic material, the core may include at least 2.10 g / cm 3 , at least 2.20g / cm 3 , 2.30g / cm 3 , at least 2.40g / cm 3 , at least 2.50g / cm 3 , at least 2.60g / cm 3 , at least 2.70g / em 3 , 2.80g / cm 3 , at least 2.90g / cm 3 , at least 3.00g / cm 3 , at least 3.10g / cm 3 , at least 3.20g / cm 3 , at least 3.30g / cm 3 , at least 3.40g / cm 3 、3.50g / cm 3 , at least 3.55g / cm3 , at least 3.60g / cm 3 , at least 3.65g / cm 3 , at least 3.70g / cm 3 , at least 3.75g / cm 3 , at least 3.80g / cm 3 , at least 3.85g / cm 3 , at least 3.90g / cm 3 , or at least 3.95g / cm 3 Additionally or alternatively, the core may contain no more than 5.80 g / cm 3 , not more than 5.70g / cm 3 , not more than 5.60g / cm 3 , not more than 5.50g / cm 3 , not more than 5.40g / cm 3 , not more than 5.30g / cm 3 , not more than 5.20g / cm 3 , not more than 5.10g / cm 3 , not more than 5.00g / cm 3 , not more than 4.90g / cm 3 , not more than 4.80g / cm 3 , not more than 4.70g / cm 3 , not more than 4.60g / cm 3 , not more than 4.50g / cm 3 , not more than 4.40g / cm 3 , not more than 4.30g / cm 3 , not more than 4.20g / cm 3 , not more than 4.10g / cm 3 , not more than 4.00g / cm 3 , or not more than 3.97g / cm 3 In yet another example, the core can have a density within a range including any of the minimum and maximum values noted herein.
[0044] In one embodiment, the core may include aluminum oxide and one or more of the following: rare earth oxides, alkaline earth oxides, or any combination thereof. In one aspect, the core may include at least 90 wt% aluminum oxide and no more than 10 wt% of one or more other oxides, based on the total weight of the core. For example, the core may include at least 93 wt% and no more than 98 wt% aluminum oxide, at least 1.5 wt% and no more than 7 wt% of one or more rare earth oxides, and up to 2 wt% alkaline earth metal oxides. In another embodiment, the core may include a specific content ratio C of rare earth oxide to alkaline earth oxide.RRO / C AEO , where C RRO is the total content of rare earth oxides, and C AEO is the total content of alkaline earth oxides. For example, the ratio C RRO / C AEO The core may have a C of no greater than 10, no greater than 9, no greater than 8, no greater than 7, no greater than 6, or no greater than 5. RRO / C AEo In addition, the ratio C RRO / C AEo The range may include any minimum and maximum values noted herein.
[0045] In another embodiment, the core may include a specific crystal structure including a primary crystalline phase containing aluminum oxide and a secondary magnetoplumbite crystalline phase containing an aluminate. In a specific embodiment, the core may include a magnetoplumbite crystalline phase containing an aluminate including one or more rare earth elements and / or one or more alkaline earth elements. In yet another embodiment, the core may include La2O3, Y2O3, or a combination thereof. In a specific example, the core may include a higher content of La2O3 than Y2O3. In another example, the core may include at least 1wt% La2O3 of the total weight of the core, such as at least 1.5wt%, at least 2wt%, at least 2.5wt%, at least 2.7wt%, at least 2.8wt%, at least 3wt%, at least 3.1wt%, or at least 3.2wt% La2O3 of the total weight of the core. Additionally or alternatively, the core may contain no more than 8 wt% La2O3, based on the total weight of the core, such as no more than 7 wt%, no more than 6 wt%, no more than 5 wt%, no more than 4 wt%, or no more than 3.5 wt% La2O3, based on the total weight of the core. Furthermore, the core may contain a La2O3 content within a range including any minimum and maximum percentages mentioned herein. In another example, the core may contain at least 0.3 wt% Y2O3, based on the total weight of the core, such as at least 0.4 wt%, at least 0.5 wt%, at least 0.6 wt%, at least 0.7 wt%, at least 0.8 wt%, at least 0.9 wt% Y2O3, based on the total weight of the core. Additionally or alternatively, the core may contain no more than 3 wt% Y2O3, based on the total weight of the core, such as no more than 2.7 wt%, no more than 2.5 wt%, no more than 2.3 wt%, no more than 2 wt%, no more than 1.7 wt%, no more than 1.5 wt%, no more than 1.3 wt%, no more than 1.1 wt%, or no more than 1% Y2O3, based on the total weight of the core. Furthermore, the core may contain a Y2O3 content within a range including any minimum and maximum percentages mentioned herein. In a particular embodiment, the core may contain a crystalline phase of magnetoplumbite containing an aluminate comprising La2O3 and Y2O3.
[0046] In a certain embodiment, the core may be substantially free of ZrO2. In at least one other embodiment, the core may include ZrO2. In another specific embodiment, the core may include a secondary magnetoplumbite crystalline phase containing MgO. In a specific example, the core may include a MgO content in the range of at least 0.5wt% to no more than 2wt% of the total weight of the core, such as in the range of at least 0.7wt% to no more than 1.6wt% of the total weight of the core, or in the range of at least 0.8wt% to no more than 1.4wt% of the total weight of the core.
[0047] In another embodiment, the core may include a specific HV hardness. For example, the core may have a HV hardness of at least 1800, at least 1850, at least 1900, at least 1920, at least 1950, at least 1970, at least 2000, at least 2100 or at least 2200. In another example, the core may have a HV hardness of not more than 2500, such as not more than 2400, not more than 2300, not more than 2200, not more than 2100, not more than 2000, not more than 1990 or not more than 1980. In addition, the core may be included in the HV hardness in the range of any minimum and maximum values mentioned herein. The HV hardness can be measured using Vickers hardness meter LM100AT according to ASTM C1327-15. Abrasive samples can be prepared as follows. Resin can be used to fix microparticles to obtain a cylindrical sample with a diameter of 25 mm, and then the surface is polished with microparticles to obtain a non-damaged surface for hardness testing.
[0048] In one embodiment, the formation process may be stopped at step 103, wherein the particles have a particle size of typically Figure 2A The structure provided in the embodiment includes a core 201 and a coating 202, wherein the coating comprises an inorganic material.
[0049] In an alternative embodiment, the process may continue to step 104 after step 103, which includes an optional process of applying an organic material. Such a process may be performed before the abrasive particles are incorporated into the fixed abrasive. According to one embodiment, the process of step 104 includes forming a second portion (e.g., 203) of the coating that covers at least some of the first portion (e.g., 202) of the coating. In one example, the second portion may include an organic-containing material. In a non-limiting embodiment, the organic-containing material may include a material that may promote bonding of the abrasive particles to the bonding material, such as an organic-containing bonding agent composition (e.g., a phenolic resin, an epoxy resin, etc.). In one particular process, the organic-containing material that may be included in the second portion may be a silane-containing material and / or a silanol-containing material. For example, according to Figure 1 The process of step 104 may include forming a second portion of the coating on the abrasive particles, wherein such particles may have a Figure 2B The general structure is provided in the examples in. The content of inorganic material mentioned herein, such as the composition of the first part 202 from the coating is based on the weight percentage of the first part.
[0050] The coating 202 may be in direct contact with the core 201. As shown, the coating 202 may be a layer covering the entire surface of the core 201. In at least one embodiment, the coating 202 may cover most of the surface of the core 201, and a portion of the core surface may not be covered by the coating 202. In a specific embodiment, the coating may include a dry material. In another embodiment, the coating may include an unsintered material.
[0051] In one embodiment, the coating can have a specific percentage of lithium content to silicon content, which can promote improved formation and properties of the abrasive particles 200. In one embodiment, the lithium can include a lithium-containing compound. In another embodiment, the lithium-containing compound can include an oxide. In another embodiment, the lithium-containing compound can include lithium oxide. In one embodiment, the silicon can include a silicon-containing compound. In another embodiment, the silicon-containing compound can include an oxide. In another embodiment, the silicon-containing compound can include silicon dioxide. In one aspect, the lithium / silicon percentage is at least 0.02%, or at least 0.03%, or at least 0.04%, or at least 0.05%, or at least 0.06%, or at least 0.07%, or at least 0.08%, at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0.9%, or at least 1.0%, or at least 1.2%, or at least 1.4%, or at least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%. In some other embodiments, the lithium / silicon percentage is no more than 25%, or no more than 24%, or no more than 23%, or no more than 22%, or no more than 21%, or no more than 20%, or no more than 19%, no more than 18%, or no more than 17%, or no more than 16%, or no more than 15%, or no more than 14%, or no more than 13%, or no more than 12%, or no more than 11%, or no more than 10%, or no more than 9%, or no more than 8%, or no more than 7%, or no more than 6%, or no more than 5%, or no more than 4%, or no more than 3%. In another example, the coating can have a lithium / silicon percentage within a range including any minimum and maximum values mentioned herein. It should be understood that all of the above ratios apply to lithium and silicon elements and their compounds, including, for example, oxides. For example, the coating can have a lithium oxide / silicon oxide (SiOx) percentage within a range including any minimum and maximum values described above for the lithium / silicon percentage. The lithium / silicon percentage is calculated by dividing the weight percentage of lithium in the coating by the weight percentage of silicon in the coating and then multiplying the calculated number by 100%. The weight percentages are those values obtained by ICP analysis of the coatings provided herein. For example, a coating comprising 0.9 wt% lithium and 90 wt% silicon would have a lithium / silicon percentage of [(0.9 wt% / 90 wt%) x 100%)] = 1%.
[0052] In one embodiment, the coating can have a specific content of lithium that can promote improved formation and properties of the abrasive grain 200. In one aspect, the content of lithium in the coating is at least 0.01 wt%, or at least 0.02 wt%, at least 0.03 wt%, at least 0.04 wt%, at least 0.05 wt%, at least 0.06 wt%, at least 0.07 wt%, at least 0.08 wt%, or at least 0.09 wt%, or at least 0.1 wt%, or at least 0.15 wt%, or at least 0.2 wt%, or to 0.25 wt%, or at least 0.3 wt%, or at least 0.35 wt%, or at least 0.4 wt%, or at least 0.5 wt%, or at least 0.6 wt%, based on the total weight of the coating. %, or at least 0.7wt%, or at least 0.8wt%, or at least 0.9wt%, or at least 1.0wt%, or at least 1.1wt%, or at least 1.2wt%, or at least 1.3wt%, or at least 1.4wt%, or at least 1.5wt%, or at least 1.6wt%, or at least 1.7wt%, or at least 1.8wt%, or at least 1.9wt%, or at least 2.0wt%, or at least 2.1wt%, or at least 2.2wt%, or at least 2.3wt%, or at least 2.4wt%, or at least 2.5wt%, or at least 2.6wt%. In some other embodiments, the lithium content is not more than 20wt%, or not more than 19wt%, or not more than 18wt%, or not more than 17wt%, or not more than 16wt%, or not more than 15wt%, or not more than 14wt%, or not more than 13wt%, or not more than 12wt%, or not more than 11wt%, or not more than 10wt%, or not more than 9wt%, or not more than 8wt%, or not more than 7wt%, or not more than 6wt%, or not more than 5wt%, or not more than 4wt%, or not more than 3wt%, or not more than 2wt%. It should be understood that the coating can have a lithium content within a range including any minimum and maximum values mentioned herein. As will be understood, the weight percentage of lithium is calculated according to the ICP analysis technique as described herein.
[0053] In yet another embodiment, the coating can have a specific percentage of potassium content to silicon content that can promote improved formation and properties of the abrasive particles 200. In one embodiment, the potassium can include a potassium-containing compound. In another aspect, the potassium-containing compound can include an oxide. In yet another embodiment, the potassium-containing compound can include potassium oxide. In one embodiment, the silicon can include a silicon-containing compound. In another aspect, the silicon-containing compound can include an oxide. In yet another embodiment, the silicon-containing compound can include silicon dioxide. In one aspect, the potassium / silicon percentage is at least 0.01%, or at least 0.02%, at least 0.03%, at least 0.04%, at least 0.05%, at least 0.06%, at least 0.07%, at least 0.08%, at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0.9%, or at least 1.0%, or at least 1.2%, or at least 1.4%, or at least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.1%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%. In still other embodiments, the potassium / silicon percentage is not greater than 40%, or not greater than 39%, or not greater than 38%, or not greater than 37%, or not greater than 36%, or not greater than 35%, or not greater than 34%, or not greater than 33%, or not greater than 32%, or not greater than 31%, or not greater than 30%, or not greater than 29%, or not greater than 28%, or not greater than 27%, or not greater than 26%, or not greater than 25%, or not greater than 24%, or not greater than 25%. In yet another example, the coating may have a potassium / silicon percentage within a range including any minimum and maximum values mentioned herein. It should be understood that all of the above ratios apply to potassium and silicon elements and compounds thereof, including, for example, oxides. For example, the coating may have a potassium oxide / silicon oxide (SiOx) percentage within a range including any minimum and maximum values described above for the potassium / silicon percentage. The potassium / silicon percentage is calculated by dividing the weight percentage of potassium in the coating by the weight percentage of silicon in the coating and then multiplying the calculated number by 100%. The weight percentages are those values obtained by ICP analysis of the coatings provided herein.For example, a coating comprising 0.9 wt% potassium and 90 wt% silicon would have a potassium / silicon percentage of [(0.9 wt% / 90 wt%) x 100%)] = 1%.
[0054] In another embodiment, the coating can have a specific content of silicon that can promote improved formation and properties of the abrasive particles 200. In one aspect, the silicon content accounts for at least 50 wt% of the total weight of the coating, at least 55 wt%, at least 60 wt%, at least 65 wt%, at least 70 wt%, at least 75 wt%, at least 80 wt%, at least 85 wt%, at least 90 wt%, at least 92 wt%, at least 95 wt% of the total weight of the coating (e.g., the first portion 202 of the coating). In some non-limiting embodiments, the silicon content can be no more than 99 wt%, no more than 98 wt%, no more than 97 wt%, or no more than 96 wt%, or no more than 95 wt%, or no more than 93 wt%, or no more than 90 wt%, or no more than 88 wt%, or no more than 85 wt%, or no more than 83 wt%, or no more than 80 wt%, or no more than 77 wt% of the total weight of the coating. In yet another example, the coating can have a silicon content within a range including any of the minimum and maximum values noted herein.As will be appreciated, the weight percent silicon is calculated according to the ICP analysis technique as described herein.
[0055] In another embodiment, the coating can have a specific content of potassium, which can promote improved formation and properties of the abrasive particles 200. In one aspect, the potassium content is at least 0.01 wt%, or at least 0.02 wt%, at least 0.03 wt%, at least 0.04 wt%, at least 0.05 wt%, at least 0.06 wt%, at least 0.07 wt%, at least 0.08 wt%, or at least 0.09 wt%, or at least 1 wt%, at least 2 wt%, at least 3 wt%, at least 4 wt%, at least 5 wt%, at least 6 wt%, at least 7 wt%, at least 8 wt%, at least 9 wt%, or at least 10 wt% of the total weight of the coating. In some other embodiments, the potassium content is no more than 30wt%, no more than 29wt%, or no more than 28wt%, or no more than 27wt%, or no more than 26wt%, or no more than 25wt%, or no more than 24wt%, or no more than 23wt%, or no more than 22wt%, or no more than 21wt%, or no more than 20wt%, or no more than 19wt%, or no more than 18wt%, or no more than 17wt%, or no more than 16wt%, or no more than 15wt%, or no more than 14wt%, or no more than 13wt%, or no more than 12wt%, or no more than 11wt%, or no more than 10wt%, or no more than 9wt%, or no more than 8wt%, or no more than 7wt% of the total weight of the coating. In yet another example, the coating can have a potassium content within a range including any minimum and maximum values mentioned herein. As will be understood, the weight percentage of potassium is calculated according to the ICP analysis technique as described herein.
[0056] In one embodiment, the coating can have a specific percentage of sodium content to silicon content that can promote improved formation and properties of the abrasive particles 200. In one embodiment, the sodium can include a sodium-containing compound. In another embodiment, the sodium-containing compound can include an oxide. In another embodiment, the sodium-containing compound can include sodium oxide. In one embodiment, the silicon can include a silicon-containing compound. In another embodiment, the silicon-containing compound can include an oxide. In another embodiment, the silicon-containing compound can include silicon dioxide. In one aspect, the sodium / silicon percentage is at least 0.01%, or at least 0.02%, at least 0.03%, at least 0.04%, at least 0.05%, at least 0.06%, at least 0.07%, at least 0.08%, or at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0.9%, or at least 1.0%, or at least 1.2%, or at least 1. 4%, or at least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%, or at least 4.2%, or at least 4.4%, or at least 4.6%, or at least 4.8%, or at least 5.0%, or at least 5.2%, or at least 5.4%, or at least 5.5%. In still other embodiments, the sodium / silicon percentage is no greater than 40%, or no greater than 39%, or no greater than 38%, or no greater than 37%, or no greater than 36%, or no greater than 35%, or no greater than 34%, or no greater than 33%, or no greater than 32%, or no greater than 31%, or no greater than 30%, or no greater than 29%, or no greater than 28%, or no greater than 27%, or no greater than 26%, or no greater than 25%, or no greater than 24%, or no greater than 23%, or no greater than 22%, or not more than 21%, or not more than 20%, or not more than 19%, or not more than 18%, or not more than 17%, or not more than 16%, or not more than 15%, or not more than 14%, or not more than 13%, or not more than 12%, or not more than 11%, or not more than 10%, or not more than 9%, or not more than 8%, or not more than 7%, or not more than 6%, or not more than 5%, or not more than 4%, or not more than 3%, or not more than 2%, or not more than 1%, or not more than 0.5%. In yet another example, the coating can have a sodium / silicon percentage within a range including any minimum and maximum values mentioned herein. It should be understood that all of the above ratios apply to sodium and silicon elements and their compounds, including, for example, oxides. For example, the coating can have a sodium oxide / silicon oxide (SiOx) percentage within a range including any minimum and maximum values described above for the sodium / silicon percentage.The sodium / silicon percentage is calculated by dividing the weight percentage of sodium in the coating by the weight percentage of silicon in the coating and then multiplying the calculated number by 100%. The weight percentages are those values obtained by ICP analysis of the coatings provided herein. For example, a coating comprising 0.9 wt% sodium and 90 wt% silicon would have a sodium / silicon percentage of [(0.9 wt% / 90 wt%) x 100%)] = 1%.
[0057] In another embodiment, the coating can have a specific content of sodium, which can promote the improved formation and properties of abrasive particles 200. On the one hand, the sodium content is at least 1wt% or at least 1.5wt% or at least 2wt%, at least 3wt%, at least 4wt%, at least 5wt%, at least 6wt%, at least 7wt%, at least 8wt%, at least 9wt%, or at least 10wt% of the total weight of the coating. In some other embodiments, the sodium content is not more than 20wt%, or not more than 19wt%, or not more than 18wt%, or not more than 17wt%, or not more than 16wt%, or not more than 15wt%, or not more than 14wt%, or not more than 13wt%, or not more than 12wt%, or not more than 11wt% of the total weight of the coating. In another example, the coating can have a sodium content in the range of any minimum and maximum values mentioned herein. As will be understood, the weight percentage of sodium is calculated according to ICP analysis techniques as described herein.
[0058] According to another non-limiting example, the coating can have a specific percentage of sodium content to lithium content that can promote improved formation and properties of the abrasive particles 200 . In one aspect, the sodium / lithium percentage is at least 0.01%, or at least 0.02%, at least 0.03%, at least 0.04%, at least 0.05%, at least 0.06%, at least 0.07%, at least 0.08%, or at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0.9%, or at least 1.0%, or at least 1.2%, or at least 1.4%, or at least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%. In some other embodiments, the sodium / lithium percentage is no more than 100%, or no more than 90%, or no more than 80%, or no more than 70%, or no more than 60%, or no more than 50%, or no more than 40%, or no more than 30%, or no more than 20%, or no more than 15%, or no more than 10%, or no more than 9%, or no more than 8%, or no more than 7%, or no more than 6%, or no more than 5%, or no more than 4%. In another example, the coating can have a sodium / silicon percentage within the range of any minimum and maximum values mentioned herein. The sodium / lithium percentage is calculated by dividing the weight percentage of sodium in the coating by the weight percentage of lithium in the coating, and then multiplying the calculated number by 100%. The weight percentage is those values obtained by ICP analysis of the coating provided herein. For example, a coating containing 0.9wt% sodium and 90wt% lithium will have a sodium / lithium percentage of [(0.9wt% / 90wt%) x 100%)] = 1%.
[0059] According to another non-limiting embodiment, the coating can have a specific percentage of sodium content to potassium content that can promote improved formation and properties of the abrasive particles 200. In one aspect, the sodium / potassium percentage is at least 0.01%, or at least 0.02%, at least 0.03%, at least 0.04%, at least 0.05%, at least 0.06%, at least 0.07%, at least 0.08%, or at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0. .9%, or at least 1.0%, or at least 1.2%, or at least 1.4%, or at least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%, or at least 5.0%, or at least 8.0 In some embodiments, the sodium / potassium ratio is no greater than 200%, or no greater than 190%, or no greater than 180%, or no greater than 170%, or no greater than 60%, or no greater than 150%, or no greater than 140%, or no greater than 130%, or no greater than 150%. In another example, the coating may have a sodium / potassium percentage within a range including any minimum and maximum values mentioned herein. The sodium / potassium percentage is calculated by dividing the weight percentage of sodium in the coating by the weight percentage of potassium in the coating and then multiplying the calculated number by 100%. The weight percentages are those values obtained by ICP analysis of the coating provided herein. For example, a coating comprising 0.9 wt% sodium and 90 wt% potassium would have a sodium / potassium percentage of [(0.9 wt% / 90 wt%) x 100%)] = 1%.
[0060] According to another non-limiting embodiment, the coating can have a specific percentage of potassium content to lithium content that can promote improved formation and properties of the abrasive grain 200. In one aspect, the potassium / lithium percentage is at least 0.01%, or at least 0.02%, at least 0.03%, at least 0.04%, at least 0.05%, at least 0.06%, at least 0.07%, at least 0.08%, or at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0.9%, or at least 1.0%, or at least 1.2%, or at least 1.4%, or at least 1.5%. At least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%, or at least 5.0%, or at least 8.0%, or at least 10%, or at least 20%, or at least 30%, or at least 40%, or at least 50%, or at least 60%, or at least 70%, or at least 80%. In yet other embodiments, the potassium / lithium percentage is no greater than 200%, or no greater than 190%, or no greater than 180%, or no greater than 170%, or no greater than 60%, or no greater than 150%, or no greater than 140%, or no greater than 130%, or no greater than 120%, or no greater than 110%, or no greater than 100%, or no greater than 90%, or no greater than 80%, or no greater than 70%, or no greater than 60%, or no greater than 50%, or no greater than 40%, or no greater than 30%, or no greater than 20%, or no greater than 15%, or no greater than 10%, or no greater than 9%, or no greater than 8%, or no greater than 7%, or no greater than 6%, or no greater than 5%, or no greater than 4%. In yet another example, the coating can have a potassium / lithium percentage within a range including any minimum and maximum values mentioned herein. The potassium / lithium percentage is calculated by dividing the weight percentage of potassium in the coating by the weight percentage of lithium in the coating and then multiplying the calculated number by 100%. The weight percentages are those values obtained by ICP analysis of the coatings provided herein. For example, a coating comprising 0.9 wt% potassium and 90 wt% lithium would have a potassium / lithium percentage of [(0.9 wt% / 90 wt%) x 100%)] = 1%.
[0061] In yet other embodiments, the coating can have a specific content of sodium compared to the lithium content, which can promote improved formation and properties of the abrasive grain 200. In one aspect, the coating comprises a sodium content of no greater than 10 times the lithium content, as measured in wt% by the ICP analysis technique described herein, or wherein the coating comprises a sodium content of no greater than 8 times the lithium content, or wherein the coating comprises a sodium content of no greater than 6 times the lithium content, or wherein the coating comprises a sodium content of no greater than 4 times the lithium content, or wherein the coating comprises a sodium content of no greater than 3 times the lithium content, or wherein the coating comprises a sodium content of no greater than 2.8 times the lithium content, or wherein the coating comprises a sodium content of no greater than 2.5 times the lithium content, or wherein the coating comprises a sodium content of no greater than 2.2 times the lithium content, or wherein the coating comprises a sodium content of no greater than 2 times the lithium content, or wherein the coating comprises a sodium content of no greater than 1.5 times the lithium content, or wherein the coating comprises a sodium content of no greater than 2.0 times the lithium content, or wherein the coating comprises a sodium content of no greater than 2.5 times the lithium content, or wherein the coating comprises a sodium content of no greater than 1.5 times the lithium content, or wherein the coating comprises a sodium content of no greater than 2.0 ...2.0 times the lithium content, or wherein the coating comprises a sodium content of no greater than 2.0 times the lithium content, or wherein the coating comprises The layer contains a sodium content of not more than 1.8 times the lithium content, or wherein the coating contains a sodium content of not more than 1.5 times the lithium content, or wherein the coating contains a sodium content of not more than 1.3 times the lithium content, or wherein the coating contains a sodium content of not more than 0.9 times the lithium content, or wherein the coating contains a sodium content of not more than 0.6 times the lithium content, or wherein the coating contains a sodium content of not more than 0.3 times the lithium content, or wherein the coating contains a sodium content of not more than 0.2 times the lithium content, or wherein the coating contains a sodium content of not more than 0.1 times the lithium content, or wherein the coating contains a sodium content of not more than 0.05 times the lithium content, or wherein the coating contains a sodium content of not more than 0.01 times the lithium content.
[0062] In yet other embodiments, the coating can have a specific content of sodium compared to the potassium content, which can promote improved formation and properties of the abrasive grains 200. In one aspect, the coating comprises a sodium content no greater than 10 times the potassium content, as measured in wt% by the ICP analysis technique described herein, or wherein the coating comprises a sodium content no greater than 8 times the potassium content, or wherein the coating comprises a sodium content no greater than 6 times the potassium content, or wherein the coating comprises a sodium content no greater than 4 times the potassium content, or wherein the coating comprises a sodium content no greater than 3 times the potassium content, or wherein the coating comprises a sodium content no greater than 2.8 times the potassium content, or wherein the coating comprises a sodium content no greater than 2.5 times the potassium content, or wherein the coating comprises a sodium content no greater than 2.2 times the potassium content, or wherein the coating comprises a sodium content no greater than 2 times the potassium content, or wherein the coating comprises a sodium content no greater than 1.5 times the potassium content, or wherein the coating comprises a sodium content no greater than 2.0 times the potassium content, or wherein the coating comprises a sodium content no greater than 2.5 times the potassium content, or wherein the coating comprises a sodium content no greater than 1.5 times the potassium content, or wherein the coating comprises a sodium content no greater than 2.0 ... The coating comprises a sodium content of no more than 1.8 times the potassium content, or wherein the coating comprises a sodium content of no more than 1.5 times the potassium content, or wherein the coating comprises a sodium content of no more than 1.3 times the potassium content, or wherein the coating comprises a sodium content of no more than 0.9 times the potassium content, or wherein the coating comprises a sodium content of no more than 0.6 times the potassium content, or wherein the coating comprises a sodium content of no more than 0.3 times the potassium content, or wherein the coating comprises a sodium content of no more than 0.2 times the potassium content, or wherein the coating comprises a sodium content of no more than 0.1 times the potassium content, or wherein the coating comprises a sodium content of no more than 0.05 times the potassium content, or wherein the coating comprises a sodium content of no more than 0.01 times the potassium content.
[0063] In one embodiment, the coating can have a specific content of a silicate-containing compound that can promote improved formation and properties of the abrasive particles 200. In a specific embodiment, the silicate-containing compound can include potassium silicate, sodium silicate, lithium silicate, or a combination thereof. In one aspect, the silicate-containing compound content accounts for at least 1 wt%, or at least 5 wt%, or at least 10 wt.%, or at least 15 wt.%, or at least 20 wt.%, or at least 30 wt.%, or at least 40 wt.%, or at least 50 wt.%, or at least 60 wt.%, or at least 70 wt.%, or at least 80 wt.%, or at least 90 wt% of the total weight of the coating. In yet other embodiments, the content of silicate-containing compounds is no more than 99 wt % of the total weight of the coating, or no more than 95 wt %, or no more than 90 wt %, or no more than 80 wt %, or no more than 70 wt %, or no more than 60 wt %, or no more than 50 wt %, or no more than 40 wt %, or no more than 30 wt %, or no more than 20 wt %, or no more than 10 wt % of the total weight of the coating. In yet another example, the coating can have a content of silicate-containing compounds within a range including any minimum and maximum values mentioned herein. As will be appreciated, the weight percentage of silicate-containing compounds is calculated according to the ICP analysis technique as described herein.
[0064] In another embodiment, the coating can have a specific content of a silica-containing compound that can promote improved formation and properties of the abrasive particles 200. In a specific embodiment, the silica-containing compound can include silica or a combination thereof. On the one hand, the content of the silica-containing compound is at least 1 wt%, or at least 5 wt%, or at least 10 wt.%, or at least 15 wt.%, or at least 20 wt.%, or at least 30 wt.%, or at least 40 wt.%, or at least 50 wt.%, or at least 60 wt.%, or at least 70 wt.%, or at least 80 wt.%, or at least 90 wt.%, based on the total weight of the coating. In yet other embodiments, the content of the silica-containing compound is no more than 99 wt % of the total weight of the coating, or no more than 95 wt %, or no more than 90 wt %, or no more than 80 wt %, or no more than 70 wt %, or no more than 60 wt %, or no more than 50 wt %, or no more than 40 wt %, or no more than 30 wt %, or no more than 20 wt %, or no more than 10 wt % of the total weight of the coating. In yet another example, the coating can have a content of silica-containing compound within a range including any minimum and maximum values mentioned herein. As will be understood, the weight percentage of the silica-containing compound is calculated according to the ICP analysis technique as described herein.
[0065] According to another non-limiting embodiment, the coating can have a specific percentage of silicate content to silica content that can promote improved formation and properties of the abrasive particles 200. In one aspect, the silicate / silicon dioxide percentage is at least 10%, or at least or at least 15%, or at least 20%, or at least 25%, or at least 30%, or at least 35%, or at least 40%, or at least 45%, at least 50%, or at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 100%. In yet other embodiments, the silicate / silicon dioxide percentage is no greater than 1000%, or no greater than 900%, or no greater than 800%, or no greater than 700%, or no greater than 600%, or no greater than 500%, or no greater than 400%, or no greater than 300%, 200%, or no greater than 190%, or no greater than 180%, or no greater than 170%, or no greater than 60%, or no greater than 150%, or no greater than 140%, or no greater than 160%. In yet another example, the coating may have a silicate / silicon dioxide percentage within a range including any minimum and maximum values mentioned herein. The silicate / silicon dioxide percentage is calculated by dividing the weight percentage of the silicate-containing compound in the coating by the weight percentage of the silica-containing compound in the coating and then multiplying the calculated number by 100%. The weight percentages are those values obtained by ICP analysis of the coating provided herein. For example, a coating comprising 0.9 wt% of a silicate-containing compound and 90 wt% of a silicate-containing compound would have a silicate / silicon dioxide percentage of [(0.9 wt% / 90 wt%) x 100%)] = 1%. In one embodiment, the abrasive grains 200 can have an average coating coverage of the core 201 surface, which can promote improved properties and performance of the abrasive grains. In one aspect, the average coating coverage can be at least 50% of the entire surface of the core, at least 55%, at least 57%, at least 59%, at least 61%, at least 63%, at least 65%, at least 68%, at least 70%, at least 72%, at least 75%, at least 76%, at least 77%, at least 79%, at least 80%, at least 82%, at least 84%, at least 85%, at least 87%, at least 88%, at least 90%, at least 91%, at least 92%, at least 93%, at least 94%, at least 95%, at least 96%, at least 97%, and at least 98%, at least 99% and no more than 100% of the entire surface of the core 201.
[0066] The coating coverage can be determined by energy dispersive spectroscopy (EDS) analysis. Image acquisition of the abrasive particles can be performed using a Merlin from Zeiss with appropriate imaging parameters. TM Field emission scanning electron microscope (FESEM) and Fast Acquisition in Bruker software are used for the analysis. For example, imaging can be performed using parameters of 7kV, 300pA and up to 10mm WD. The abrasive particles can be coated with Au / Pd for 30 seconds before image acquisition. Using EDS, the elements of the abrasive particles can be quantified and used as an indication of whether the points of the core are covered by the first part. 1% Si can be used as a threshold of 1% Si, and the quantitative chemical analysis for each point can be simplified to a binomial (covered or not covered). The number of Au / Pd coatings and C elements are not considered in the analysis. The 95% confidence interval (95% CI) can be used in a binomial distribution calculator, such as the Binomial Probability Confidence Interval Calculator (Version 4.0) available at www.dianelsoper.com, to calculate the reported confidence interval. For example, when 53 of 60 points indicate greater than 1% Si, the number of trials entered into the calculator is 60 and the number of successes is 53. At 95% CI, coverage ranged from 77% to 95%.
[0067] In another embodiment, the coating 202 can have a substantially uniform thickness. In one embodiment, the thickness of the coating 202 can vary along the surface of the core 201 .
[0068] In another embodiment, abrasive grain 200 can include the average thickness of coating 202, which can promote the formation and property of the improvement of abrasive grain. For example, the average thickness of coating 202 can be at least 10nm, at least 12nm, at least 15nm, at least 18nm, at least 20nm, at least 25nm, at least 28nm, at least 30nm, at least 32nm, at least 35nm, at least 38nm, at least 40nm, at least 43nm, at least 45nm, at least 48nm, at least 50nm, at least 52nm, at least 55nm, at least 58nm, at least 60nm, at least 63nm, at least 68nm, at least 70nm, at least 74nm, at least 76nm, at least 80nm, at least 83nm, at least 86nm, at least 90nm. In another example, the average thickness of coating 202 of abrasive grain 200 can be not more than 150nm, not more than 140nm, not more than 130nm, not more than 120nm, not more than 110nm, not more than 100nm. Additionally, the average thickness of the coating 202 of the abrasive grains 200 can be within a range including any minimum and maximum values noted herein. For example, the abrasive grains can include an average thickness of the coating 202 within a range of 10 nm to 150 nm or within a range of 80 nm to 100 nm.
[0069] In yet another embodiment, the abrasive grains 200 can include a specific thickness standard deviation of the coating 202 that can promote improved formation of the abrasive grains and improved performance of the abrasive grains. In one aspect, the absolute value of the thickness standard deviation can be no greater than 200% of the average thickness, no greater than 150%, no greater than 100%, no greater than 80%, no greater than 50%, no greater than 49%, no greater than 47%, no greater than 44%, no greater than 42%, no greater than 40%, no greater than 38%, no greater than 36%, no greater than 34%, no greater than 33%, no greater than 31%, no greater than 30%, no greater than 29%, no greater than 27%, no greater than 38%, no greater than 36%, no greater than 34%, no greater than 33%, no greater than 31%, no greater than 30%, no greater than 29%, no greater than 27%, no greater than 38%, no greater than 36%, no greater than 34%, no greater than 35%, no greater than 36%, no greater than 37%, no greater than 38%, no greater than 38%, no greater than 36%, no greater than 37 ... Greater than 25%, no greater than 23%, no greater than 21%, no greater than 20%, no greater than 19%, no greater than 18%, no greater than 17%, no greater than 16%, no greater than 14%, no greater than 12%, no greater than 11%, no greater than 10%, no greater than 9%, no greater than 8%, no greater than 7%, no greater than 6%, no greater than 5%, no greater than 4%, no greater than 3%, no greater than 2%, no greater than 1%, no greater than 0.8%, no greater than 0.7%, or no greater than 0.5%. On the other hand, abrasive grain can comprise the absolute value of thickness standard deviation, and it is at least 0.001% of average thickness, at least 0.05%, at least 0.08%, at least 0.1%, at least 0.2%, at least 0.3%, at least 0.4%, at least 0.5%, at least 0.7%, at least 0.8%, at least 0.9%, at least 1%, at least 1.2%, at least 1.5%, at least 1.8%, at least 2%, at least 2.2%, at least 2.5%, at least 2.8%, at least 3%, at least 4% or at least 5% of the average thickness of coating.In addition, abrasive grain can comprise the thickness standard deviation of coating, and this thickness standard deviation has the absolute value in the scope that comprises any minimum value and maximum value mentioned herein.
[0070] In another aspect, the abrasive grains may include a coating 202 having a thickness standard deviation of at least 1 nm, at least 3 nm, at least 5 nm, at least 7 nm, at least 9 nm, at least 10 nm, at least 13 nm, at least 15 nm, at least 17 nm, at least 19 nm, at least 21 nm, at least 23 nm, at least 25 nm, at least 28 nm, at least 30 nm, at least 32 nm, at least 34 nm, at least 36 nm, at least 39 nm, at least 41 nm, at least 45 nm, at least 46 nm, at least 47 nm, at least 48 nm, at least 49 nm, at least 50 nm, at least 51 nm, at least 52 nm, at least 53 nm, at least 54 nm, at least 55 nm, at least 56 nm, at least 57 nm, at least 58 nm, at least 59 nm, at least 60 nm, at least 61 nm, at least 62 nm, at least 63 nm, at least 64 nm, at least 65 nm, at least 66 nm, at least 67 nm, at least 68 nm, at least 69 nm, at least 70 nm, at least 71 nm, at least 72 nm, at least 73 nm, at least 74 nm, at least 75 nm, at least 76 nm, at least 77 nm, at least 78 nm, at least 79 nm, 48nm, or at least 50nm, at least 60nm, at least 70nm, at least 80nm, at least 100nm, at least 110nm, at least 120nm, at least 130nm, at least 140nm, at least 150nm, at least 160nm, at least 170nm, at least 180nm, at least 190nm, at least 210nm, at least 220nm, or at least 230nm, at least 240nm, at least 250nm, at least 260nm, at least 270nm, or at least 280nm. On the other hand, the thickness standard deviation can be no more than 500nm, no more than 480nm, no more than 460nm, no more than 420nm, no more than 400nm, no more than 350nm, no more than 320nm, no more than 310nm, no more than 300nm, no more than 280nm, no more than 260nm, no more than 230nm, no more than 210nm, no more than 190nm, no more than 170nm, no more than 150nm, no more than 130nm, no more than 120nm, no more than 110nm, no more than 100nm, no more than 90nm, no more than 80nm, no more than 70nm, no more than 60nm, no more than 50nm, no more than 40nm, no more than 30nm, no more than 20nm, no more than 18nm, no more than 15nm, no more than 12nm, no more than 10nm or no more than 5nm. In addition, the thickness standard deviation of coating can be in the scope of any minimum and maximum values mentioned herein. In a specific example, the thickness standard deviation of the coating may be in the range of 10 nm to 400 nm, or in the range of 30 nm to 300 nm, or in the range of 50 nm to 200 nm.
[0071] In one embodiment, the coating 202 can include an amorphous phase including silicon dioxide. In another specific aspect, the coating 202 can include a specific amount of an amorphous phase that can promote improved formation and properties of the abrasive grains 210 and abrasive articles including the abrasive grains 210. For example, at least 90 vol% or at least 95 vol% of the coating 202 can be an amorphous phase. In another specific aspect, the coating 202 consists essentially of an amorphous phase.
[0072] In another aspect, coating 202 can include an amorphous phase and a crystalline phase of silicon dioxide. In another specific aspect, coating 202 can include an amorphous phase consisting essentially of silicon dioxide and a crystalline phase consisting essentially of silicon dioxide.
[0073] In one aspect, the coating, in particular the first portion 202 of the coating, can have a specific crystalline content that can improve the manufacture and / or performance of the abrasive grains and / or the fixed abrasive articles containing these abrasive grains. For example, the coating can have a specific crystalline content (i.e., single crystal or polycrystalline), including, for example but not limited to, a crystalline content of at least 1 vol% of the total volume of the first portion 202, such as at least 3 vol%, or at least 5 vol%, or at least 7 vol%, or at least 10 vol%, or at least 12 vol%, or at least 15 vol% of the total volume of the coating (in particular the first portion 202). In a non-limiting embodiment, the total crystalline content of the coating (e.g., the first portion 202) may be limited due to the lack of high temperature sintering. For example, in one non-limiting embodiment, the coating (e.g., first portion 202) can have a total crystalline content of no more than 99 vol% of the total volume of the coating or the first portion 202 of the coating, such as no more than 97 vol%, or no more than 90 vol%, or no more than 80 vol%, or no more than 70 vol%, or no more than 60 vol%, or no more than 50 vol%, or no more than 40 vol%, or no more than 30 vol%, or no more than 20 vol%, or no more than 10 vol%, or no more than 8 vol%, or no more than 5 vol%, or no more than 3 vol%, or no more than 2 vol%, of the total volume of the coating or the first portion 202 of the coating, and can have no more than 1 vol% of the total volume of the coating. In addition, the coating 202 can include a crystalline content within a range including any minimum percentage and maximum percentage mentioned herein. In a specific embodiment, the first portion 202 of the coating can be substantially free of a crystalline phase.
[0074] In another specific embodiment, the coating, such as the first portion 202 of the coating, can include an amorphous phase that accounts for a major amount of the total volume of the first portion, such as an amorphous phase that accounts for at least 55 vol% of the total volume of the first portion 202, such as an amorphous content of at least 60 vol%, or at least 70 vol%, or at least 80 vol%, or at least 90 vol%, or at least 95 vol% of the total volume of the first portion 202 of the coating of abrasive particles. In a specific example, the first portion 202 can be substantially composed of an amorphous phase material. For example, in a specific embodiment, the first portion 202 can include a mixture of amorphous silicon dioxide and an amorphous silicate.
[0075] The crystallinity can be determined by performing an X-ray diffraction (also referred to as "XRD" in this disclosure) analysis on a powder sample of the coating 202 prepared as follows. The first material can be placed in an alumina crucible and heated in a furnace at the sintering temperature mentioned in the embodiments of this article for 30 minutes. The crucible can then be removed from the furnace and cooled at ambient temperature (i.e., 20°C to 25°C). The solid can be recovered from the crucible and manually ground, such as using a mortar and pestle, to obtain a powder sample of the coating 202. XRD can be obtained using a copper X-ray source with a Cu Kα wavelength of 1.54 angstroms in a Bragg-Brentano configuration (the standard for powder XRD). Identification of the crystalline phase can be performed using EVA Bruker AXS software or other equivalent software and the ICDD-PDF4+ database (2020 version). The crystallinity can be determined by Rietveld refinement using TOPAS 4.2 software from Bruker or other equivalent software that follows the Corindon Al2O3 standard.
[0076] In an embodiment, the first portion of the coating can include domains having a particular average domain size, which can promote improved formation and performance of the abrasive particles.
[0077] In another embodiment, the coating may include nanoparticles and a binder material. In a specific embodiment, the coating may include agglomerated particles comprising nanoparticles bonded by a binder material. On the one hand, the binder material may include silicon and oxygen. In a specific aspect, the binder material may include a silicate, such as a silicate comprising one or more alkali metals. In a specific example, the binder material may include a silicate comprising lithium and optionally another alkali metal, such as sodium, potassium, or any combination thereof. In an even more specific example, the binder material may consist essentially of lithium silicate. On the other hand, the nanoparticles may include silicon and oxygen. In a specific aspect, the nanoparticles may include silicon dioxide.
[0078] In another embodiment, the coating may include nanopores, such as pores having a pore size of no greater than 800 nm, no greater than 700 nm, no greater than 600 nm, no greater than 500 nm, no greater than 400 nm, no greater than 300 nm, no greater than 200 nm, no greater than 100 nm, no greater than 90 nm, no greater than 80 nm, no greater than 70 nm, no greater than 60 nm, no greater than 50 nm, no greater than 40 nm, no greater than 30 nm, no greater than 20 nm, no greater than 10 nm, no greater than 8 nm, or no greater than 6 nm. Additionally or alternatively, the coating may include pores having a pore size of at least 1 nm, at least 5 nm, at least 7 nm, at least 10 nm, at least 20 nm, at least 30 nm, at least 40 nm, at least 50 nm, at least 60 nm, at least 70 nm, at least 80 nm, at least 90 nm, at least 100 nm, at least 200 nm, or at least 30 nm. Additionally, the coating can include pores having a size within a range including any of the minimum and maximum values noted herein.
[0079] In another embodiment, the coating may include a specific content, such as at least 0.0001% by volume of the total volume of the abrasive grain, or at least 0.0005%, at least 0.001%, at least 0.005%, at least 0.01%, at least 0.05%, at least 0.1%, at least 0.5%, or at least 1% by volume of pores accounting for the total volume of the abrasive grain. Additionally or alternatively, the coating may include no more than 10% by volume of the total volume of the abrasive grain, no more than 9%, no more than 8%, no more than 7%, no more than 6%, no more than 5%, no more than 4%, no more than 3%, no more than 2%, no more than 1%, no more than 0.5%, no more than 0.1%, no more than 0.05%, no more than 0.01%, or no more than 0.005% by volume of pores. Moreover, the coating can comprise a porosity content within a range comprising any of the minimum and maximum percentages noted herein.
[0080] In another embodiment, the coating may comprise at least 51% of the theoretical density, such as at least 55%, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, or at least 90% of the theoretical density. Additionally or alternatively, the coating may comprise no more than 98% of the theoretical density, such as no more than 95%, no more than 93%, no more than 90%, or no more than 88% of the theoretical density. Furthermore, the coating may comprise a density within a range including any minimum and maximum percentages mentioned herein. In yet another embodiment, the core may comprise a higher density than the coating.
[0081] In an embodiment, the coating may include a specific roughness that may contribute to improved properties and / or performance of the abrasive particles.
[0082] In another embodiment, the coating may include a specific coverage on the core, which may be conducive to the improved properties and / or performance of the abrasive particles. In one example, the coating coverage may be at least 75% of the surface area of the core, such as at least 80%, at least 85%, at least 90%, or at least 93% of the surface area of the core. In another example, the coating coverage may be no more than 99% of the surface area of the core, such as no more than 97%, no more than 95%, no more than 93%, no more than 90%, or no more than 88% of the surface area of the core. In addition, the coating coverage may be within the scope of any minimum percentage and maximum percentage mentioned herein.
[0083] In an embodiment, the coating may include a certain average number of discrete nanoparticles per certain area (loose nanoparticles), which may contribute to improved properties and / or performance of the abrasive particles.
[0084] Figure 3 Atomic force microscopy (also referred to in this disclosure as "AFM") phase images of abrasive particles are included. Figure 3 An image of a core 301 including a die 310 is included.
[0085] In one embodiment, abrasive grain can comprise the average crystal domain size of at least 50nm, at least 55nm, at least 60nm, at least 65nm, at least 70nm, at least 75nm, at least 80nm, at least 90nm, at least 100nm, at least 200nm, at least 300nm, at least 400nm, at least 500nm or at least 600nm.On the other hand, abrasive grain can comprise the average crystal domain size greater than nm or greater than the coating of 26nm.In a particular aspect, abrasive grain can comprise the average crystal domain size not more than 3mm, not more than 2mm, not more than 1mm, not more than 0.5mm, not more than 0.1mm, not more than 0.01mm or not more than 0.001mm.In addition, abrasive grain can be included in the average crystal domain size in the scope comprising any minimum and maximum values mentioned above.As used herein, average crystal domain size is intended to refer to the mean value of the maximum size of at least 20 identifiable crystal domains in the phase diagram of randomly selected abrasive grain. The crystal domain size of the abrasive grains was measured by scanning electron microscopy (SEM) of the polished section of the abrasive grains. A magnification of 50,000x was used and the samples were thermally etched at 100°C for 5 minutes. The crystal domain size was obtained by the intercept method without statistical correction.
[0086] In one embodiment, the abrasive grains can include a specific standard deviation in domain size that can promote improved formation and performance of the abrasive grains. In one aspect, the standard deviation in domain size can have no greater than 50% of the average domain size, no greater than 49% of the average domain size of the coating, no greater than 48%, no greater than 47%, no greater than 46%, no greater than 45%, no greater than 44%, no greater than 43%, no greater than 42%, no greater than 41%, no greater than 40%, no greater than 39%, no greater than 38%, no greater than 37%, no greater than 36%, no greater than 35%, no greater than 33%, no greater than 31%, no greater than 30%, no greater than 29%, no greater than 27%, no greater than 25%, no greater than 23%, no greater than 21%, no greater than 20%, no greater than 19 ... No more than 17%, no more than 16%, no more than 15%, no more than 49%, no more than 48%, no more than 47%, no more than 46%, no more than 45%, no more than 43%, no more than 42%, no more than 41%, no more than 40%, no more than 39%, no more than 37%, no more than 35%, no more than 33%, no more than 30%, no more than 28%, no more than 26%, no more than 24%, no more than 21%, no more than 19%, no more than 17%, no more than 15%, no more than 13%, no more than 11%, no more than 10%, no more than 9%, no more than 8%, no more than 7%, or no more than 5% in absolute value. On the other hand, abrasive grain can comprise the standard deviation of the crystal domain size of at least 0.001% of the crystal domain size of coating, at least 0.01% of the crystal domain size of coating, at least 0.1%, at least 1%, at least 2%, at least 4%, at least 3% or at least 5% absolute value. In addition, abrasive grain can be included in the standard deviation with absolute value in the scope that comprises any minimum and maximum value mentioned herein.
[0087] In another embodiment, the abrasive particles may comprise a standard deviation having an absolute value of no greater than 65 nm, no greater than 63 nm, no greater than 61 nm, no greater than 60 nm, no greater than 58 nm, no greater than 55 nm, no greater than 53 nm, no greater than 51 nm, no greater than 50 nm, no greater than 49 nm, no greater than 47 nm, no greater than 45 nm, no greater than 43 nm, no greater than 41 nm, no greater than 40 nm, no greater than 38 nm, no greater than 36 nm, no greater than 32 nm, no greater than 30 nm, no greater than 28 nm, no greater than 25 nm, no greater than 23 nm, no greater than 22 nm, no greater than 20 nm, no greater than 19 nm, no greater than 17 nm, no greater than 16 nm, no greater than 15 nm, no greater than 14 nm, no greater than 13 nm, or no greater than 12 nm. On the other hand, abrasive grain can comprise the standard deviation of the crystal domain size with at least 0.1nm, at least 0.3nm, at least 0.5nm, at least 1nm, at least 2nm, at least 3nm, at least 4nm, at least 5nm, at least 6nm, at least 7nm, at least 8nm, at least 9nm, at least 10nm, at least 11nm, at least 12nm, at least 13nm, at least 14nm, at least 15nm, at least 16nm or at least 17nm absolute value.In addition, standard deviation can have the absolute value in the scope that comprises any minimum and maximum value mentioned herein.
[0088] refer to Figure 1 , the process can continue to frame 104 to form a second portion of the coating covering at least a portion of the core. Forming the second portion can include treating the core with a second coating. In one embodiment, the second coating can include a coupling agent, for example, a silicon-containing compound, such as a silane or another organosilicon compound. In particular, the second coating can include an organosilicon coupling agent, which can provide an improved combination between a surface having an -OH functional group and an organic polymer material. For example, the second coating can include an organosilicon having an amino, alkoxy, alkyl alkoxy, alkyl trialkoxy, vinyl, propenyl, methacryl, mercapto or other functional groups or any combination thereof. Specific examples of silanes can include aminosilanes, including, for example, bisaminosilane, aminoalkyltrialkoxysilane, aminoethyltriethoxysilane, aminopropyltriethoxysilane, phenylaminoalkyltrialkoxysilane or any combination thereof. Further examples of organosilicon compounds can include siloxanes, siloxane fluids, silsesquioxanes, etc., or any combination thereof.
[0089] In an exemplary embodiment, the core can be wetted with a solution comprising a silane in a solvent such as water or ethanol. The concentration of the silane can be in the range of, for example, 2 vol% to 6 vol%. In other embodiments, in-situ spraying or other methods known in the art can be used to coat the core with a second coating.
[0090] Forming the second portion of the coating may further include drying the coated core, wet or otherwise. For the second portion of the coating, drying may be performed at a temperature of 20° C. to 180° C. for 10 minutes to up to 36 hours.
[0091] According to one embodiment, after applying the second part 203, the abrasive grains finally formed can include a specific content of silane-containing compounds, including, for example, but not limited to, at least 0.02wt% of the total weight of the coating containing silane compounds. In another embodiment, the coating can include at least 0.5wt% of the total weight of the coating, such as at least 1wt%, or at least 2wt%, or at least 3wt%, or at least 4wt%, or at least 5wt%, or at least 6wt%, or at least 7wt%, or at least 8wt%, or at least 9wt%, or at least 10wt% of the silane-containing compounds. In addition, in another non-limiting embodiment, the coating can include no more than 25wt% of the total weight of the coating, such as no more than 20wt%, or no more than 18wt%, or no more than 16wt%, or no more than 14wt%, or no more than 12wt%, or no more than 10wt% of the silane-containing compounds of the total weight of the coating. It should be understood that the coating can be included in the silane-containing compound content within the range including any minimum and maximum values mentioned above.
[0092] refer to Figure 2B , a cross-section of an abrasive particle 210 is provided and represents an abrasive particle according to an alternative embodiment. In one embodiment, the abrasive particle 210 may include a core 201 and a coating 205 covering the core 201. The coating 205 may include a first portion 202 covering the core 201 and a second portion 203 covering the first portion 202 and the core 201. The first portion 202 may be located between the surface of the core 201 and the second portion 203. In a non-limiting embodiment, the abrasive particle 210 may be formed by first forming the abrasive particle 210 by using steps 101, 102, and 103. Figure 2A The abrasive particles provided in step 104 and secondly as provided in step 104 form a second portion 203 covering the first portion of the core.
[0093] In one non-limiting embodiment, the second portion 203 may be in direct contact with the first portion 202. In one embodiment, the second portion 203 may cover the entire surface of the core 201, the entire first portion 202, or both. In one embodiment, the second portion 203 may cover a majority of the first portion 202. For example, a portion of the first portion 202 may not be covered by the second portion 203. In one embodiment, a portion of the core surface may be in direct contact with the second portion 203. In yet another embodiment, the second portion 203 may be bonded to the first portion 202 and to the core 201.
[0094] In one embodiment, the second portion 203 of the coating 205 may include a silane or a silane reaction product. A silane reaction product is intended to refer to a silane derivative that may be formed during the process of forming the coating. For example, a suitable silane or silane reaction product may include 3-aminopropyltriethoxysilane.
[0095] In one embodiment, the abrasive particles 210 or 201 may include an average content of the coating 205 or 202 of at least 0.01 wt.% based on the weight of the core 201, such as at least 0.02 wt.%, at least 0.03 wt.%, at least 0.04 wt.%, at least 0.05 wt.%, at least 0.06 wt.%, at least 0.07 wt.%, at least 0.08 wt.%, at least 0.09 wt.%, at least 0.1 wt.%, at least 0.15 wt.%, at least 0.16 wt.%, at least 0.17 wt.%, at least 0.18 wt.%, at least 0.19 wt.%, at least 0.2 wt.%, at least 0.25 wt.%, at least 0.26 wt.%, at least 0.27 wt.%, at least 0.28 wt.%, at least 0.29 wt.%, or at least 0.3 wt.%, based on the weight of the core 201. As used herein, the average content of the coating 205 or 202 may be an average of the coating contents of at least 5 abrasive grains 210 or 201 . In another example, the abrasive particles 210 or 201 may include an average content of the coating 205 or 202 of no more than 1 wt.% of the weight of the core 201, such as no more than 0.9 wt.%, no more than 0.8 wt.%, no more than 0.7 wt.%, no more than 0.6 wt.%, no more than 0.55 wt.%, no more than 0.5 wt.%, no more than 0.48 wt.%, no more than 0.46 wt.%, no more than 0.45 wt.%, no more than 0.43 wt.%, no more than 0.42 wt.%, no more than 0.41 wt.%, no more than 0.4 wt.%, no more than 0.38 wt.%, no more than 0.37 wt.%, no more than 0.36 wt.%, no more than 0.35 wt.%, or no more than 0.34 wt.%, based on the weight of the core 201. Moreover, the abrasive particles 210 can comprise an average content of the coating 205 within a range comprising any of the minimum and maximum percentages noted herein.
[0096] In one embodiment, the abrasive particles 210 can include a particular average thickness of the coating 205 that can promote improved formation and properties of the abrasive particles 210. For example, the abrasive particles 210 can include an average thickness of the coating 205 of no greater than 10 microns, no greater than 9 microns, no greater than 8 microns, no greater than 7 microns, no greater than 6 microns, no greater than 5 microns, no greater than 4 microns, no greater than 3 microns, no greater than 2 microns, no greater than 1 micron, no greater than 0.9 microns, no greater than 0.8 microns, no greater than 0.7 microns, no greater than 0.6 microns, no greater than 0.5 microns, no greater than 0.4 microns, no greater than 0.3 microns, or no greater than 0.2 microns. In another example, the abrasive particles 210 can include an average thickness of at least 0.05 microns, at least 0.06 microns, at least 0.07 microns, at least 0.08 microns, at least 0.09 microns, at least 0.1 microns, at least 0.11 microns, at least 0.12 microns, at least 0.13 microns, at least 0.14 microns, at least 0.15 microns, at least 0.16 microns, at least 0.17 microns, at least 0.18 microns, at least 0.19 microns, at least 0.20 microns, at least 0.21 microns, at least 0.22 microns, at least 0.24 microns, at least 0.26 microns, at least 0.28 microns, at least 0.29 microns, at least 0.30 microns, or at least 0.31 microns of the coating 205. In addition, the abrasive particles 210 can include an average thickness of the coating 205 within a range including any minimum and maximum percentages mentioned herein. As used herein, the average thickness of the coating 205 may refer to an average value of the thickness of the coating 205 of at least five abrasive grains 210 .
[0097] In one embodiment, the abrasive particles 210 or 201 can include a specific ratio of the average thickness of the coating 205 or 202, respectively, to the average particle size of the core 201, which can promote improved formation and properties of the abrasive particles 210. For example, the ratio can be less than 1, such as not greater than 0.9, not greater than 0.7, not greater than 0.5, not greater than 0.4, not greater than 0.2, not greater than 0.1, not greater than 0.08, not greater than 0.06, not greater than 0.05, not greater than 0.03, not greater than 0.02, not greater than 0.01, not greater than 0.009, not greater than 0.008, not greater than 0.007, not greater than 0.006, not greater than 0.005, not greater than 0.004, not greater than 0.003, not greater than 0.002, or not greater than 0.1. In another example, the ratio of the average thickness of the coating 205 or 202 to the average grain size of the core 201 can be at least 0.0005, at least 0.0007, at least 0.0009, at least 0.001, at least 0.002, at least 0.003, at least 0.004, at least 0.005, at least 0.006, at least 0.007, at least 0.008, at least 0.009, at least 0.01, at least 0.02, or at least 0.03. In addition, the ratio of the average thickness of the coating 205 or 202 to the average grain size of the core 201 can be within a range including any minimum and maximum percentages mentioned herein. As used herein, the average grain size of the core 201 is intended to refer to the D of the core 201. 50 .
[0098] In one embodiment, the abrasive particles 210 and 201 may include an average particle size (i.e., D) of at least 10 microns, at least 30 microns, at least 40 microns, at least 50 microns, at least 60 microns, at least 70 microns, at least 80 microns, at least 90 microns, at least 100 microns, at least 120 microns, at least 140 microns, at least 150 microns, at least 170 microns, at least 180 microns, at least 200 microns, at least 210 microns, at least 230 microns, at least 250 microns, at least 260 microns, at least 270 microns, at least 290 microns, at least 300 microns, at least 320 microns, at least 340 microns, at least 350 microns, at least 360 microns, at least 380 microns, at least 400 microns, at least 420 microns, at least 430 microns, at least 440 microns, at least 450 microns, at least 460 microns, at least 470 microns, at least 490 microns, or at least 500 microns. 50). In another embodiment, abrasive particles 210 and 201 can include an average particle size of not more than 3 mm, such as not more than 2 mm, not more than 1.8 mm, not more than 1.6 mm, not more than 1.5 mm, not more than 1.2 mm, not more than 1 mm, not more than 900 microns, not more than 850 microns, not more than 830 microns, not more than 800 microns, not more than 750 microns, not more than 700 microns, not more than 650 microns, not more than 600 microns, not more than 550 microns, not more than 500 microns, not more than 450 microns or not more than 400 microns. In addition, abrasive particles 210 and 201 can be included in the average particle size within the scope of any minimum and maximum values mentioned herein.
[0099] It should be noted that, compared with corresponding conventional abrasive grains, the abrasive grains of embodiments herein can have improved features, properties and / or performance.As used herein, corresponding conventional abrasive grains are intended to relate to the abrasive grains with the core identical with the abrasive grains of embodiments herein and coating, and difference is that the coating of conventional abrasive grains is formed using a process different from the abrasive grains of embodiments herein.The feature of this improvement of abrasive grains can include the uniformity of the average thickness of morphology, coating coverage, coating, the thickness of coating, such as the standard deviation of coating thickness, the average crystal domain size of coating, the standard deviation coating of the crystal domain size of coating or their combination in any.Especially, the abrasive grains of embodiments herein have statistically relevant sample sizes, and all samples about abrasive grains describe improved features, properties and performance. In another example, abrasive grain can be the abrasive grain of at least 1kg, the abrasive grain of at least 2kg, the abrasive grain of at least 4kg, the abrasive grain of at least 5kg, the abrasive grain of at least 7kg, the abrasive grain of at least 8kg, the abrasive grain of at least 10kg, the abrasive grain of at least 20kg, the abrasive grain of at least 30kg, the abrasive grain of at least 50kg, the abrasive grain of at least 100kg, the abrasive grain of at least 250kg, at least 500kg or the abrasive grain of at least 1 ton.In another example, abrasive grain can constitute the significant percentage of the abrasive grain from the fixed grinding article.In another example, at least 100 abrasive grains, at least 500 abrasive grains, at least 1000 abrasive grains, at least 2000 abrasive grains, at least 5000 abrasive grains, at least 8000 abrasive grains, at least 10000 abrasive grains or at least 500000 abrasive grains.
[0100] It is also worth noting that the variables and parameters of the process of this paper embodiment are controlled and / or are suitable for promoting the formation of improved coating properties and the abrasive grains with improved characteristics, properties and performance.Compared with corresponding conventional abrasive grains, the process of this paper embodiment can promote the formation of abrasive grains with improved quality.For example, drying conditions, silicon dioxide concentration, mixing conditions and / or other process characteristics as described in this paper embodiment can help reduce the formation of agglomerates of abrasive grains and prevent the deterioration of core material, and form improved coating.Abrasive grain can comprise conformal and uniform coating.
[0101] In yet another embodiment, the abrasive grains 201 or 210 can comprise an anti-aging factor that is at least 5% better than a plurality of corresponding conventional abrasive grains, at least 8% better, at least 10% better, at least 12% better, at least 15% better, at least 18% better, at least 20% better, at least 22% better, at least 24% better, at least 25% better, at least 28% better, at least 30% better, at least 32% better, at least 35% better, at least 36% better, at least 38% better, or at least 40% better than a plurality of corresponding conventional abrasive grains.
[0102] In one embodiment, coating 202 or 205 can have a specific hardness, which can promote the improved performance and / or properties of abrasive particles and abrasive products. On the one hand, the hardness can be greater than 1GPa, such as at least 1.5GPa, at least 1.8GPa, at least 2GPa, at least 2.2GPa, at least 2.5GPa, at least 2.8GPa or at least 3GPa. On the other hand, the hardness can be less than 10GPa, such as less than 8GPa, at most 7GPa, at most 6GPa, at most 5GPa, at most 4GPa, at most 3.8GPa, at most 3.5GPa, at most 3.3GPa, at most 3.2GPa or at most 3GPa. On the other hand, coating 202 or 205 can have a hardness in the range of any minimum and maximum values mentioned herein. Hardness can be determined as follows. The prepared suspension can be deposited on a flat aluminum oxide substrate (purity 99.5%) by dip coating. The coated substrate can be dried as described in the embodiments of this article. Nanoindentation can be performed on the coated plate. Up to 20 indentations can be made to determine the hardness of the coating.
[0103] Figure 4 A cross-sectional view of a bonded abrasive article 400 comprising a body 401 including abrasive grains 210 contained within a bonding material 403 is included. In at least one embodiment, the bonding material 403 defines an interconnected and continuous phase throughout the volume of the body 401. In another embodiment, the bonding material 403 can form a three-dimensional matrix. In another embodiment, the abrasive grains 201 can be used alone or in combination with the abrasive grains 210 to form the abrasive article 400.
[0104] In one embodiment, the abrasive particles 210 can be bonded to the bonding material 403. In yet another embodiment, a portion of the coating 203 can be cross-linked to the bonding material 403. For example, silane or a silane derivative can be cross-linked to the bonding material during the process of forming the body 401.
[0105] In one embodiment, bonding material 403 may include organic material, inorganic material, ceramic material, glass material, metal or metal alloy material. In a specific embodiment, bonding material 403 may include organic material, such as one or more natural organic materials, synthetic organic materials or their combination. In a specific example, organic material may be made of resin, which may include thermosetting plastics, thermoplastics and their combination. For example, some suitable resins may include phenolic resin, epoxy resin, polyester, cyanate ester, shellac, polyurethane, polybenzoxazine, polybismaleimide, polyimide, rubber and their combination.
[0106] The phenolic resin can be modified with a curing agent or cross-linking agent, such as hexamethylenetetramine. At temperatures exceeding about 90°C, some examples of hexamethylenetetramine can form cross-links to form methylene and dimethylene amino bridges that help cure the resin. The hexamethylenetetramine can be uniformly dispersed within the resin. More specifically, the hexamethylenetetramine can be uniformly dispersed within the resin region as a cross-linking agent. Even more specifically, the phenolic resin can include resin regions having cross-linked domains of submicron average size.
[0107] In one embodiment, the body 401 may include a certain amount of bonding material 403, which may promote improved formation of the abrasive article. In one example, the body 401 may include no more than 98 vol%, or no more than 95 vol%, or no more than 90 vol%, or no more than 85 vol%, or no more than 80 vol%, or no more than 75 vol%, or no more than 70 vol%, or no more than 65 vol%, or no more than 60 vol%, or no more than 55 vol%, or no more than 50 vol%, or no more than 45 vol%, or no more than 40 vol%, or no more than 35 vol%, or no more than 30 vol%, or no more than 25 vol% of the bonding material 403 of the total volume of the body. In another example, the body 401 may include at least 1 vol%, or at least 2 vol%, or at least 5 vol%, or at least 10 vol%, or at least 20 vol%, or at least 30 vol%, or at least 35 vol%, or at least 40 vol%, or at least 45 vol% of the total volume of the body. In addition, the body 401 may include the bonding material 403 in an amount including any minimum percentage and maximum percentage mentioned herein.
[0108] In an embodiment, the body 401 can include a content of abrasive particles 210 and / or 201 that can contribute to improved properties and performance of the abrasive article. In one example, the body 401 may include no more than 65 vol% abrasive particles 210, such as no more than 64 vol%, or no more than 62 vol%, or no more than 60 vol%, or no more than 58 vol%, or no more than 56 vol%, or no more than 54 vol%, or no more than 52 vol%, or no more than 50 vol%, or no more than 48 vol%, or no more than 46 vol%, or no more than 44 vol%, or no more than 42 vol%, or no more than 40 vol%, or no more than 38 vol%, or no more than 36 vol%, or no more than 34 vol%, or no more than 32 vol%, or no more than 30 vol%, or no more than 28 vol%, or no more than 26 vol%, or no more than 24 vol%, or no more than 22 vol%, or no more than 20 vol%. In another example, the body 901 may include at least 1 vol% of abrasive particles 210 and / or 201, such as at least 2 vol%, or at least about 4 vol%, or at least 6 vol%, or at least 8 vol%, or at least 10 vol%, or at least 12 vol%, or at least 14 vol%, or at least 16 vol%, or at least 18 vol%, or at least 20 vol%, or at least 25 vol%, or at least 30 vol%, or at least 35 vol% of abrasive particles 210 and / or 201, based on the total volume of the body 401. In addition, the body 401 may include an amount of abrasive particles 210 and / or 201 within a range including any minimum and maximum percentages mentioned herein.
[0109] In at least one embodiment, the body 401 may include abrasive particles, which include a core 201 having at least one different characteristic, including composition, shape, hardness, particle size, brittleness, toughness, grain size, or any combination thereof. For example, the core 201 may include shaped abrasive particles and non-shaped particles or abrasive particles with different shapes. In another example, the core 201 may include a first type of abrasive particles and a second type of abrasive particles, the first type of abrasive particles including high-quality abrasive particles (e.g., fused alumina, alumina-zirconia, seeded sol-gel alumina, shaped abrasive particles, etc.), and the second type of abrasive particles including diluent abrasive particles.
[0110] refer to Figure 4, the body 401 further includes a central opening 430 and an axial axis 931 extending axially through the central opening 430, which can be perpendicular to the radial axis extending in a direction defining the diameter (d) of the body. It should be understood that any other fillers and / or phases (e.g., porosity) of the body can be contained within the bonding material 403.
[0111] In one embodiment, the body 401 may include a porosity type selected from the group consisting of: closed porosity, open porosity, and combinations thereof. In one aspect, most of the porosity may be closed porosity defined by discrete pores, and in a particular aspect, the porosity may consist essentially of closed porosity. In another aspect, most of the porosity may be open, defining a network of interconnected channels extending through at least a portion of the body, and in a particular aspect, substantially all of the porosity may be open porosity. In yet another aspect, the porosity may include a combination of open porosity and closed porosity.
[0112] In one embodiment, the body 401 may include a specific porosity that may promote improved properties and performance of the abrasive article. In one example, the body 401 may include a porosity of at least 1 vol%, or at least 2 vol%, or at least 4 vol%, or at least 6 vol%, or at least 8 vol%, or at least 10 vol%, or at least 12 vol%, or at least 14 vol%, or at least 16 vol%, or at least 18 vol%, or at least 20 vol%, or at least 25 vol%, or at least 30 vol%, or at least 40 vol%, or at least 45 vol%, or at least 50 vol%, or at least 55 vol% of the total volume of the body. In another example, the body 401 may include a porosity of no more than 80 vol%, or no more than 75 vol%, or no more than 70 vol%, or no more than 65 vol%, or no more than 60 vol%, or no more than 55 vol%, or no more than 50 vol%, or no more than 45 vol%, or no more than 40 vol%, or no more than 35 vol%, or no more than 30 vol%, or no more than 25 vol%, or no more than 20 vol%, or no more than 15 vol%, or no more than 10 vol%, or no more than 5 vol%, or no more than 2 vol% of the total volume of the body. It should be understood that the body 401 may include a porosity within a range including any minimum percentage and maximum percentage mentioned herein. The porosity of the body 401 was measured using a mercury porosimetry (Micromeritics AutoPore IV9520) to quantify the porosity in the body. A 1 cm x 1 cm x 1 cm sample was cut from the body and measured at low pressure (50 μmHg) and high pressure (equilibrium time 10 seconds) to obtain the bulk density and apparent density of the body. The porosity was then calculated by the following equation: (Porosity = [100-(bulk density / apparent density)].
[0113] In one embodiment, the body 401 may include fillers. For example, the body 401 may include fillers not greater than 40vol% of the total volume of the body. In a specific example, the body 401 may have fillers not greater than 35vol%, such as not greater than 30vol%, or not greater than 25vol%, or not greater than 20vol%, or not greater than 15vol%, or not greater than 10vol%, or not greater than 8vol%, or not greater than 5vol%, or not greater than 4vol%, or even not greater than 3vol%. For at least one embodiment, the body 401 may not have fillers. According to a non-limiting embodiment, the body 401 may have fillers of at least 0.05vol% of the total volume of the body 401, such as at least 0.5vol%, or at least 1vol%, or at least 2vol%, or at least 3vol%, or at least 5vol%, or at least 10vol%, or at least 15vol%, or at least 20vol%, or even at least 30vol%. Furthermore, the filler within body 401 can be within a range between any of the minimum and maximum percentages noted above, including, for example but not limited to, a content within a range of at least 0.5 vol % and no greater than 30 vol %.
[0114] The filler may include a material selected from the group consisting of powder, particles, spheres, fibers, and combinations thereof. In addition, in a specific example, the filler may include an inorganic material, an organic material, a fiber, a woven material, a nonwoven material, a particle, a mineral, a nut, a shell, an oxide, an aluminum oxide, a carbide, a nitride, a boride, a polymer material, a naturally occurring material, and a combination thereof. In a certain embodiment, the filler may include a material such as sand, hollow aluminum oxide balls, chromite, magnesite, dolomite, hollow mullite balls, borides, titanium dioxide, carbon products (e.g., carbon black, coke, or graphite), silicon carbide, wood powder, clay, talc, hexagonal boron nitride, molybdenum disulfide, feldspar, nepheline syenite, glass balls, glass fibers, CaF2, KBF4, cryolite (Na3AlF6), potassium cryolite (K3AlF6), pyrite, ZnS, copper sulfide, mineral oil, fluoride, carbonate, calcium carbonate, silica fume stone, mullite, steel, iron, copper, brass, bronze, tin, aluminum, kyanite, andalusite, garnet, quartz, fluoride, mica, nepheline syenite, sulfates (e.g., barium sulfate), carbonates (e.g., calcium carbonate), titanates (e.g., potassium titanate fibers), rock wool, clay, sepiolite, iron sulfides (e.g., Fe2S3, FeS2, or combinations thereof), potassium fluoroborate (KBF4), zinc borate, borax, boric acid, fine corundum powder, P15A, cork, glass spheres, silica microspheres (Z-ray), silver, Saran TM Resin, p-dichlorobenzene, oxalic acid, alkali halide, organic halide, attapulgite or any combination thereof.
[0115] In at least one embodiment, the filler may include a material selected from the group consisting of: an antistatic agent, a lubricant, a porosity inducing agent, a colorant, and combinations thereof. In a specific example where the filler is a particulate material, the filler may be different from the abrasive particles, with an average particle size significantly smaller than the abrasive particles.
[0116] The cross-section of the body 401 is shown as having a generally rectangular shape, which may represent a wheel or disk shape with a central opening 430, such that it is an annulus. It should be understood that the abrasive articles of the embodiments herein may have a body that may be a honing, cone, cup, flange shape, cylinder, wheel, ring, and combinations thereof.
[0117] The body 401 can have a generally circular shape viewed from above. It should be understood that in three dimensions, the body 401 can have a certain thickness (t) so that the body 401 has a disk-like or cylindrical shape. As shown, the body 401 can have an outer diameter (d) extending through the center of the body 401. The central opening 430 can extend through the entire thickness (t) of the body 401 so that the abrasive article 400 can be mounted on a spindle or other machine for rotating the abrasive article 400 during operation. According to one embodiment, the body 401 can have a specific relationship between the thickness (t) and the diameter (d) so that the aspect ratio (d:t) of the body is at least 10:1, such as at least 20:1, or at least 30:1, or at least 40:1, or at least 50:1, or at least 60:1, or at least 70:1, or at least 80:1, or at least 90:1, or at least 100:1. Furthermore, in one non-limiting embodiment, the aspect ratio (d:t) can be no greater than 1000: 1, or no greater than 500: 1. It will be appreciated that the aspect ratio (d:t) can be within a range including any of the minimum and maximum values noted above.
[0118] In one aspect, a fixed abrasive article 400 according to an embodiment can have a moisture retention value, wherein the moisture retention value is measured by dividing the wet MOR value of the fixed abrasive article by the dry MOR value of the fixed abrasive article and multiplying by 100. In a particular embodiment, the fixed abrasive article can have a moisture retention value of at least 70%, such as at least 71%, or at least 72%, or at least 73%, or at least 74%, or at least 75%, or at least 76%, or at least 77%, or at least 78%, or at least 79%, or at least 80%, or at least 81%, or at least 82%, or at least 83%, or at least 84%, or even at least 85%. In addition, in a non-limiting embodiment, the moisture retention value can be no greater than 99.9%, or no greater than 99.5%, or no greater than 99%, or no greater than 98%, or no greater than 96%, or no greater than 94%, or no greater than 92%, or no greater than 90%. It should be understood that the moisture retention value can be within any range including the above minimum and maximum values. The 3-point bend test was measured on a universal testing machine using the following parameters: test speed of 1.27 mm / min, support span of 50.8 mm, and load cell of 10 kN. The 3-point bend test was performed on a strip sample representing the abrasive article 400 having dimensions of 4.0×1.0×0.5 inches. At least three samples were tested to obtain the maximum flexural stress (i.e., modulus of rupture (MOR)) of the abrasive article.
[0119] Figure 5 An illustration of a process of forming an abrasive article including a body is included. At block 601, the process can include forming a mixture including a bond material and / or a bond precursor material and abrasive grains.
[0120] According to one embodiment, the bonding material and / or bonding precursor material may include a material selected from the group consisting of organic materials, organic precursor materials, inorganic materials, inorganic precursor materials, natural materials, and combinations thereof. In a specific example, the bonding material may include a metal or a metal alloy (such as a powdered metal material, or a precursor of a metal material) that is suitable for forming a metal bonding matrix material during further processing.
[0121] According to another embodiment, the mixture may include a glassy material or a precursor of a glassy material suitable for forming a glassy bonding material during further processing. For example, the mixture may include a glassy material in powder form, including, for example, oxygen-containing materials, oxides or oxide composites, glass frits, and any combination thereof.
[0122] In yet another embodiment, the mixture may include a ceramic material or a precursor of a ceramic material suitable for forming a ceramic bonding material during further processing. For example, the mixture may include a ceramic material in powder form, including, for example, oxygen-containing materials, oxides or oxide composites, and any combination thereof.
[0123] According to another embodiment, the mixture may include an organic material or a precursor of an organic material, which is suitable for forming an organic bonding material during further processing. Such organic materials may include one or more natural organic materials, synthetic organic materials, and combinations thereof. In a specific example, the organic material may be made of a resin, which may include a thermosetting plastic, a thermoplastic, and combinations thereof. For example, some suitable resins may include phenolic resins, epoxy resins, polyesters, cyanates, shellac, polyurethanes, polybenzoxazine, polybismaleimide, polyimide, rubber, and combinations thereof. In a specific embodiment, the mixture includes an uncured resin material, which is configured to form a phenolic resin bonding material by further processing.
[0124] The phenolic resin can be modified with a curing agent or cross-linking agent, such as hexamethylenetetramine. At temperatures exceeding about 90°C, some examples of hexamethylenetetramine can form cross-links to form methylene and dimethylene amino bridges that help cure the resin. The hexamethylenetetramine can be uniformly dispersed within the resin. More specifically, the hexamethylenetetramine can be uniformly dispersed within the resin region as a cross-linking agent. Even more specifically, the phenolic resin can include resin regions having cross-linked domains of submicron average size.
[0125] Other materials, such as fillers, may be included in the mixture. The filler may or may not be present in the final formed abrasive article. After forming the mixture, the method for forming the abrasive article may further include forming a green body comprising abrasive particles, which are contained in a bonding material. The green body is an unprocessed body that can be further processed before forming the final formed abrasive article. The formation of the green body may include the following techniques, such as pressing, molding, casting, printing, spraying, and combinations thereof. In a particular embodiment, the formation of the green body may include pressing the mixture into a specific shape, including, for example, performing a pressing operation to form a green body in the form of a grinding wheel.
[0126] It should also be understood that one or more reinforcing materials can be included in the mixture, or between the parts of the mixture, to form a composite body, which includes one or more grinding parts (i.e., abrasive particles contained in the bonding material and porosity, filler, etc.) and a reinforcing part made of reinforcing materials. Some suitable examples of reinforcing materials include woven materials, non-woven materials, glass fibers, fibers, natural materials, synthetic materials, inorganic materials, organic materials, or any combination thereof. As used herein, terms such as "reinforced" or "reinforced" refer to discrete layers or parts of reinforcing materials, which are different from the bonding materials and grinding materials used to make the grinding parts. Terms such as "internal reinforcement" or "internal reinforcement" indicate that these components are in the body of the abrasive article or embedded in the body of the abrasive article. In a cutting wheel, the internal reinforcement component can be, for example, a disc shape with a central opening to accommodate the spindle hole of the wheel. In some wheels, the reinforcing material extends from the spindle hole to the periphery of the body. In other cases, the reinforcing material can extend from the periphery of the body to a point just below the flange for fixing the body. Some abrasive articles may be "zone reinforced" where the (internal) fiber reinforcement component is around the spindle bore and flange areas of the body (approximately 50% of the body diameter).
[0127] After forming a mixture having the desired composition and applying the mixture to the desired processing equipment, the method can continue by processing the mixture to form the final formed abrasive article. Some suitable processing examples may include curing, heating, sintering, crystallization, polymerization, pressing and combinations thereof. In one example, the process may include a binder batching, mixing abrasive particles with a binder or a bonding precursor material, filling a mold, pressing and heating or curing the mixture.
[0128] After the processing is completed, an abrasive article, such as abrasive article 400, is formed, including abrasive grains and any other additives contained in the bond material.
[0129] Figure 6 A cross-sectional view of a coated abrasive article 600 is included, which includes a substrate 601, a make coat 602 covering the substrate 601, and abrasive grains 210. The coated abrasive article 600 may optionally include fillers, additives, or any combination thereof. A size coat 603 covers and is bonded to the abrasive grains 210 and the make coat 602. In another embodiment, the abrasive grains 200 may be used or combined with the abrasive grains 210 to form the coated abrasive article 600.
[0130] In one embodiment, substrate 601 can include organic materials, inorganic materials and combinations thereof. In some instances, substrate 601 can include woven materials. However, substrate 601 can be made of nonwoven materials. Particularly suitable substrate materials can include organic materials, including polymers, especially polyester, polyurethane, polypropylene, polyimide such as KAPTON of DuPont, paper or any combination thereof. Some suitable inorganic materials can include metals, metal alloys, especially foils of copper, aluminum, steel and combinations thereof.
[0131] The primer layer 602 can be applied to the surface of the substrate 601 in a single process, or alternatively, the abrasive grains 210 can be combined with the primer layer 602 material and the combination of the primer layer 602 and the abrasive grains 210 can be applied to the surface of the substrate 601 as a mixture. In some examples, by separating the process of applying the primer layer 602 from the process of depositing the abrasive grains 210 in the primer layer 602, the controlled deposition or placement of the abrasive grains 210 in the primer layer 602 can be better suited. In addition, it is conceivable that such processes can be combined. Suitable primer layer 602 materials can include organic materials, particularly polymer materials, including, for example, polyester, epoxy resin, polyurethane, polyamide, polyacrylate, polymethacrylate, polyvinyl chloride, polyethylene, polysiloxane, silicone, cellulose acetate, cellulose nitrate, natural rubber, starch, shellac and mixtures thereof. In one embodiment, the primer layer 602 can include polyester resin. The coated substrate can then be heated to cure the resin and bonded abrasive grains 210 to the substrate 601. Typically, during this curing process, the coated substrate 601 may be heated to a temperature of about 100°C to less than about 250°C.
[0132] After fully forming the make coat 602 in which the abrasive grains 210 are accommodated, the size layer 603 can be formed to cover the bonded abrasive grains 210 and bond the bonded abrasive grains to the make coat 602 and the substrate 601. The size layer 603 can include an organic material and can be made essentially of a polymer material, and it is worth noting that polyester, epoxy resin, polyurethane, polyamide, polyacrylate, polymethacrylate, polyvinyl chloride, polyethylene, polysiloxane, silicone, cellulose acetate, nitrocellulose, natural rubber, starch, shellac, and mixtures thereof can be used.
[0133] Many different aspects and embodiments are feasible. Some of those aspects and embodiments are described herein. After reading this specification, those skilled in the art will appreciate that those aspects and embodiments are merely illustrative and do not limit the scope of the invention. Embodiments may be based on any one or more embodiments listed below.
[0134] Example
[0135] Embodiment 1. An abrasive particle comprising:
[0136] A subject, the subject comprising:
[0137] core, and
[0138] A coating covering at least a portion of the core, wherein the coating comprises at least one of the following:
[0139] a) a lithium / silicon percentage in a range of at least 0.01% to no more than 25%;
[0140] b) a potassium / silicon percentage in the range of at least 0.01% to no more than 40%;
[0141] c) a sodium / silicon percentage in the range of at least 0.01% to no more than 40%; or
[0142] d) any combination thereof.
[0143] Embodiment 2. The abrasive grain of embodiment 1, wherein the lithium / silicon percentage is at least 0.02%, at least 0.03%, at least 0.04%, at least 0.05%, at least 0.06%, at least 0.07%, at least 0.08%, or at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0.9%, or at least 1.0%, or at least 1.2%, or at least 1.4%, or at least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%.
[0144] Embodiment 3. Abrasive grains according to embodiment 1, wherein the lithium / silicon percentage is not greater than 24%, or not greater than 23%, or not greater than 22%, or not greater than 21%, or not greater than 20%, or not greater than 19%, or not greater than 18%, or not greater than 17%, or not greater than 16%, or not greater than 15%, or not greater than 14%, or not greater than 13%, or not greater than 12%, or not greater than 11%, or not greater than 10%, or not greater than 9%, or not greater than 8%, or not greater than 7%, or not greater than 6%, or not greater than 5%, or not greater than 4%, or not greater than 3%.
[0145] Embodiment 4. Abrasive particles according to embodiments 1 and 82 to 84, wherein the coating comprises at least 0.01 wt%, or at least 0.02 wt%, at least 0.03 wt%, at least 0.04 wt%, at least 0.05 wt%, at least 0.06 wt%, at least 0.07 wt%, at least 0.08 wt%, or at least 0.09 wt%, or at least 0.1 wt%, or at least 0.15 wt%, or at least 0.2 wt%, or at least 0.25 wt%, or at least 0.3 wt%, or at least 0.35 wt%, or at least 0.4 wt%, or at least 0.5 wt%, or at least %, or at least 1.8 wt%, or at least 1.9 wt%, or at least 2.0 wt%, or at least 2.1 wt%, or at least 2.2 wt%, or at least 2.3 wt%, or at least 2.4 wt%, or at least 2.5 wt%, or at least 2.6 wt% lithium content.
[0146] Embodiment 5. Abrasive grains according to any one of embodiments 1, 4 and 82 to 84, wherein the coating comprises a lithium content of not more than 20wt%, or not more than 19wt%, or not more than 18wt%, or not more than 17wt%, or not more than 16wt%, or not more than 15wt%, or not more than 14wt%, or not more than 13wt%, or not more than 12wt%, or not more than 11wt%, or not more than 10wt%, or not more than 9wt%, or not more than 8wt%, or not more than 7wt%, or not more than 6wt%, or not more than 5wt%, or not more than 4wt%, or not more than 3wt%, or not more than 2wt%.
[0147] Embodiment 6. Abrasive grains according to any one of embodiments 1, 4 to 5 and 82 to 84, wherein the coating comprises a silicon content of at least 80 wt%, at least 81 wt%, at least 82 wt%, at least 83 wt%, at least 84 wt%, at least 85 wt%, at least 86 wt%, at least 87 wt%, at least 88 wt%, at least 89 wt%, at least 90 wt%, at least 91 wt%, at least 92 wt%, at least 93 wt%, at least 94 wt%, or at least 95 wt%.
[0148] Embodiment 7. Abrasive grain according to any one of embodiments 1, 4 to 6 and 82 to 84, wherein the coating comprises a silicon content of not greater than 99 wt%, not greater than 98 wt%, not greater than 97 wt%, or not greater than 96 wt%.
[0149] Embodiment 8. The abrasive grain of embodiment 1, wherein the potassium / silicon percentage is at least 0.02%, at least 0.03%, at least 0.04%, at least 0.05%, at least 0.06%, at least 0.07%, at least 0.08%, or at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0. 8%, or at least 0.9%, or at least 1.0%, or at least 1.2%, or at least 1.4%, or at least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.1%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%.
[0150] Embodiment 9. The abrasive grain of embodiment 1, wherein the potassium / silicon percentage is not greater than 39%, or not greater than 38%, or not greater than 37%, or not greater than 36%, or not greater than 35%, or not greater than 34%, or not greater than 33%, or not greater than 32%, or not greater than 31%, or not greater than 30%, or not greater than 29%, or not greater than 28%, or not greater than 27%, or not greater than 26%, or not greater than 25%, or not greater than 24%. %, or not more than 23%, or not more than 22%, or not more than 21%, or not more than 20%, or not more than 19%, or not more than 18%, or not more than 17%, or not more than 16%, or not more than 15%, or not more than 14%, or not more than 13%, or not more than 12%, or not more than 11%, or not more than 10%, or not more than 9%, or not more than 8%, or not more than 7%, or not more than 6%, or not more than 5%, or not more than 4%.
[0151] Embodiment 10. Abrasive grains according to any one of embodiments 1 and 82 to 84, wherein the coating comprises a potassium content of at least 0.01 wt%, or at least 0.02 wt%, at least 0.03 wt%, at least 0.04 wt%, at least 0.05 wt%, at least 0.06 wt%, at least 0.07 wt%, at least 0.08 wt%, or at least 0.09 wt%, or at least 1 wt%, at least 2 wt%, at least 3 wt%, at least 4 wt%, at least 5 wt%, at least 6 wt%, at least 7 wt%, at least 8 wt%, at least 9 wt%, or at least 10 wt%.
[0152] Embodiment 11. Abrasive grains according to any one of embodiments 1, 10 and 82 to 84, wherein the coating comprises a potassium content of not more than 30 wt%, not more than 29 wt%, or not more than 28 wt%, or not more than 27 wt%, or not more than 26 wt%, or not more than 25 wt%, or not more than 24 wt%, or not more than 23 wt%, or not more than 22 wt%, or not more than 21 wt%, or not more than 20 wt%, or not more than 19 wt%, or not more than 18 wt%, or not more than 17 wt%, or not more than 16 wt%, or not more than 15 wt%, or not more than 14 wt%, or not more than 13 wt%, or not more than 12 wt%, or not more than 11 wt%, or not more than 10 wt%, or not more than 9 wt%, or not more than 8 wt%, or not more than 7 wt%.
[0153] Embodiment 12. Abrasive particles according to any one of embodiments 1 and 82 to 84, wherein the coating comprises not more than 39%, or not more than 38%, or not more than 37%, or not more than 36%, or not more than 35%, or not more than 34%, or not more than 33%, or not more than 32%, or not more than 31%, or not more than 30%, or not more than 29%, or not more than 28%, or not more than 27%, or not more than 26%, or not more than 25%, or not more than 24%, or not more than 23%, or not more than 24%. 2%, or not more than 21%, or not more than 20%, or not more than 19%, or not more than 18%, or not more than 17%, or not more than 16%, or not more than 15%, or not more than 14%, or not more than 13%, or not more than 12%, or not more than 11%, or not more than 10%, or not more than 9%, or not more than 8%, or not more than 7%, or not more than 6%, or not more than 5%, or not more than 4%, or not more than 3%, or not more than 2%, or not more than 1%, or not more than 0.5% sodium / silicon percentage.
[0154] Embodiment 13. Abrasive grain according to any one of embodiments 1, 12, and 82 to 84, wherein the coating comprises at least 0.02%, at least 0.03%, at least 0.04%, at least 0.05%, at least 0.06%, at least 0.07%, at least 0.08%, or at least 0.1%, or at least 0.2%, or at least 0.3%, or at least 0.4%, or at least 0.5%, or at least 0.6%, or at least 0.7%, or at least 0.8%, or at least 0.9%, or at least 1.0%, or at least 1.2%. , or at least 1.4%, or at least 1.6%, or at least 1.8%, or at least 2.0%, or at least 2.2%, or at least 2.4%, or at least 2.6%, or at least 2.8%, or at least 3.0%, or at least 3.2%, or at least 3.4%, or at least 3.6%, or at least 3.8%, or at least 4.0%, or at least 4.2%, or at least 4.4%, or at least 4.6%, or at least 4.8%, or at least 5.0%, or at least 5.2%, or at least 5.4%, or at least 5.5% sodium / silicon percentage.
[0155] Embodiment 14. Abrasive particles according to any one of embodiments 1, 12, 13 and 82 to 84, wherein the coating comprises not more than 30 wt%, not more than 29 wt%, or not more than 28 wt%, or not more than 27 wt%, or not more than 26 wt%, or not more than 25 wt%, or not more than 24 wt%, or not more than 23 wt%, or not more than 22 wt%, or not more than 21 wt%, or not more than 20 wt%, or not more than 19 wt%, or not more than 24 wt%. A sodium content of greater than 18wt%, or not greater than 17wt%, or not greater than 16wt%, or not greater than 15wt%, or not greater than 14wt%, or not greater than 13wt%, or not greater than 12wt%, or not greater than 11wt%, or not greater than 10wt%, or not greater than 9wt%, or not greater than 8wt%, or not greater than 7wt%, or not greater than 6wt%, or not greater than 5wt%, or not greater than 4wt%, or not greater than 3wt%, or not greater than 2wt%.
[0156] Embodiment 15. Abrasive grains according to any one of embodiments 1, 12 to 14 and 82 to 84, wherein the coating comprises a sodium content of at least 0.01 wt%, or at least 0.05 wt%, or at least 0.1 wt%, or at least 0.2 wt%, or at least 0.3 wt%, or at least 0.5 wt%, or at least 1.0 wt%, or at least 1.5 wt%, or at least 2.0 wt%.
[0157] Embodiment 16. Abrasive particles according to any one of embodiments 1 and 4 to 7, wherein the coating comprises a sodium content of not more than 10 times the lithium content as measured in wt %, or wherein the coating comprises a sodium content of not more than 8 times the lithium content, or wherein the coating comprises a sodium content of not more than 6 times the lithium content, or wherein the coating comprises a sodium content of not more than 4 times the lithium content, or wherein the coating comprises a sodium content of not more than 3 times the lithium content, or wherein the coating comprises a sodium content of not more than 2.8 times the lithium content, or wherein the coating comprises a sodium content of not more than 2.5 times the lithium content, or wherein the coating comprises a sodium content of not more than 2.2 times the lithium content, or wherein the coating comprises a sodium content of not more than 2 times the lithium content. amount, or wherein the coating comprises a sodium content of not more than 1.8 times the lithium content, or wherein the coating comprises a sodium content of not more than 1.5 times the lithium content, or wherein the coating comprises a sodium content of not more than 1.3 times the lithium content, or wherein the coating comprises a sodium content of not more than 0.9 times the lithium content, or wherein the coating comprises a sodium content of not more than 0.6 times the lithium content, or wherein the coating comprises a sodium content of not more than 0.3 times the lithium content, or wherein the coating comprises a sodium content of not more than 0.2 times the lithium content, or wherein the coating comprises a sodium content of not more than 0.1 times the lithium content, or wherein the coating comprises a sodium content of not more than 0.05 times the lithium content, or wherein the coating comprises a sodium content of not more than 0.01 times the lithium content.
[0158] Embodiment 17. Abrasive grains according to any one of embodiments 1, 10 and 11, wherein the coating comprises a sodium content of no greater than 10 times the potassium content as measured in wt %, or wherein the coating comprises a sodium content of no greater than 8 times the potassium content, or wherein the coating comprises a sodium content of no greater than 6 times the potassium content, or wherein the coating comprises a sodium content of no greater than 4 times the potassium content, or wherein the coating comprises a sodium content of no greater than 3 times the potassium content, or wherein the coating comprises a sodium content of no greater than 2.8 times the potassium content, or wherein the coating comprises a sodium content of no greater than 2.5 times the potassium content, or wherein the coating comprises a sodium content of no greater than 2.2 times the potassium content, or wherein the coating comprises a sodium content of no greater than 2 times the potassium content. content, or wherein the coating comprises a sodium content of not more than 1.8 times the potassium content, or wherein the coating comprises a sodium content of not more than 1.5 times the potassium content, or wherein the coating comprises a sodium content of not more than 1.3 times the potassium content, or wherein the coating comprises a sodium content of not more than 0.9 times the potassium content, or wherein the coating comprises a sodium content of not more than 0.6 times the potassium content, or wherein the coating comprises a sodium content of not more than 0.3 times the potassium content, or wherein the coating comprises a sodium content of not more than 0.2 times the potassium content, or wherein the coating comprises a sodium content of not more than 0.1 times the potassium content, or wherein the coating comprises a sodium content of not more than 0.05 times the potassium content, or wherein the coating comprises a sodium content of not more than 0.01 times the potassium content.
[0159] Embodiment 18 The abrasive grain of any one of embodiments 1, 4 to 7, and 16, wherein the lithium comprises a lithium-containing compound.
[0160] Embodiment 19 The abrasive grain of Embodiment 18, wherein the lithium-containing compound comprises an oxide.
[0161] Embodiment 20 The abrasive grain of Embodiment 18, wherein the lithium-containing compound comprises lithium oxide.
[0162] Embodiment 21. The abrasive grain of any one of Embodiments 1 and 82 to 84, wherein the silicon comprises a silicon-containing compound.
[0163] Embodiment 22. The abrasive grain of Embodiment 21, wherein the silicon-containing compound comprises an oxide.
[0164] Embodiment 23. The abrasive grain of Embodiment 21, wherein the silicon-containing compound comprises silicon dioxide.
[0165] Embodiment 24. The abrasive grain of embodiment 1, wherein the potassium comprises a potassium-containing compound.
[0166] Embodiment 25. The abrasive grain of Embodiment 24, wherein the potassium-containing compound comprises an oxide.
[0167] Embodiment 26. The abrasive grain of embodiment 24, wherein the potassium-containing compound comprises potassium oxide.
[0168] Embodiment 27. The abrasive grain of embodiment 1, wherein the sodium comprises a sodium-containing compound.
[0169] Embodiment 28. The abrasive grain of Embodiment 27, wherein the sodium-containing compound comprises an oxide.
[0170] Embodiment 29. The abrasive grain of Embodiment 27, wherein the sodium-containing compound comprises sodium oxide.
[0171] Embodiment 30 The abrasive particle of Embodiment 1, wherein the core comprises a ceramic material.
[0172] Embodiment 31. Abrasive particles according to any one of embodiments 1 and 82 to 84, wherein the core comprises oxides, carbides, nitrides, superabrasives, borides, carbon oxides, nitrogen oxides, carbon-based materials, agglomerates, aggregates, shaped abrasive particles, microcrystalline materials, nanocrystalline materials, or any combination thereof.
[0173] Embodiment 32. The abrasive grain of any one of embodiments 1 and 82 to 84, wherein the core comprises an oxide selected from the group consisting of aluminum oxide, silicon dioxide, zirconium oxide, or any combination thereof.
[0174] Embodiment 33. The abrasive grain of any one of embodiments 1 and 82 to 84, wherein the core comprises fused alumina, sol-gel alumina, nanocrystalline alumina, brown fused alumina, or any combination thereof.
[0175] Embodiment 34. The abrasive grain of any one of Embodiments 1 and 82 to 84, wherein the core comprises a polycrystalline material made of a plurality of crystalline grains, wherein the crystalline grains have an average crystal domain size of at least 50 nm and no greater than 3 mm.
[0176] Embodiment 35 The abrasive grain of any one of Embodiments 1 and 82 to 84, wherein the core comprises at least one of: a single crystalline phase, a polycrystalline phase, an amorphous phase, or any combination thereof.
[0177] Embodiment 36. Abrasive grains according to any one of embodiments 1 and 82 to 84, wherein the coating comprises a total crystalline content of not more than 99 vol%, or not more than 97 vol%, or not more than 90 vol%, or not more than 80 vol%, or not more than 70 vol%, or not more than 60 vol%, or not more than 50 vol%, or not more than 40 vol%, or not more than 30 vol%, or not more than 20 vol%, or not more than 10 vol%, or not more than 8 vol%, or not more than 5 vol%, or not more than 3 vol%, or not more than 2 vol%, or not more than 1 vol%, based on the total volume of the coating.
[0178] Embodiment 37. Abrasive particles according to any one of embodiments 1 and 82 to 84, wherein the core comprises at least 2.10 g / cm3, at least 2.20 g / cm3, 2.30 g / cm3, at least 2.40 g / cm3, at least 2.50 g / cm3, at least 2.60 g / cm3, at least 2.70 g / cm3, 2.80 g / cm3, at least 2.90 g / cm3, at least 3.00 g / cm3, at least 3.10 g / cm3, cm3, at least 3.20 g / cm3, at least 3.30 g / cm3, at least 3.40 g / cm3, 3.50 g / cm3, at least 3.55 g / cm3, at least 3.60 g / cm3, at least 3.65 g / cm3, at least 3.70 g / cm3, at least 3.75 g / cm3, at least 3.80 g / cm3, at least 3.85 g / cm3, at least 3.90 g / cm3, or at least 3.95 g / cm3.
[0179] Embodiment 38. Abrasive particles according to any one of embodiments 1 and 82 to 84, wherein the core comprises a density of no greater than 5.80 g / cm3, no greater than 5.70 g / cm3, no greater than 5.60 g / cm3, no greater than 5.50 g / cm3, no greater than 5.40 g / cm3, no greater than 5.30 g / cm3, no greater than 5.20 g / cm3, no greater than 5.10 g / cm3, no greater than 5.00 g / cm3, no greater than 4.90 g / cm3, no greater than 4.80 g / cm3, no greater than 4.70 g / cm3, no greater than 4.60 g / cm3, no greater than 4.50 g / cm3, no greater than 4.40 g / cm3, no greater than 4.30 g / cm3, no greater than 4.20 g / cm3, no greater than 4.10 g / cm3, no greater than 4.00 g / cm3, or no greater than 3.97 g / cm3.
[0180] Embodiment 39. Abrasive grain according to any one of embodiments 1 and 82 to 84, wherein the core comprises a density of at least 80% of its theoretical density, at least 85%, at least 88%, at least 90%, at least 92%, at least 95%, or at least 98% of its theoretical density.
[0181] Embodiment 40. Abrasive particles according to any one of embodiments 1 and 82 to 84, wherein the core comprises a porosity of no more than 10 vol%, no more than 9 vol%, no more than 8 vol%, no more than 7 vol%, no more than 6 vol%, no more than 5 vol%, no more than 4 vol%, no more than 3 vol%, no more than 2 vol%, or no more than 1 vol%, of the total volume of the core.
[0182] Embodiment 41. The abrasive grain of any one of Embodiments 1 and 82 to 84, wherein the core comprises substantially no pores.
[0183] Embodiment 42. The abrasive grain of any one of Embodiments 1 and 82 to 84, wherein the coating comprises a dry material.
[0184] Embodiment 43. The abrasive grain of any one of Embodiments 1 and 82 to 84, wherein the coating comprises unsintered material.
[0185] Embodiment 44. Abrasive particles according to any one of embodiments 1 and 82 to 84, wherein the coating comprises an average coating thickness of at least 10 nm, at least 12 nm, at least 15 nm, at least 18 nm, at least 20 nm, at least 25 nm, at least 28 nm, at least 30 nm, at least 32 nm, at least 35 nm, at least 38 nm, at least 40 nm, at least 43 nm, at least 45 nm, at least 48 nm, at least 50 nm, at least 52 nm, at least 55 nm, at least 58 nm, at least 60 nm, at least 63 nm, at least 68 nm, at least 70 nm, at least 74 nm, at least 76 nm, at least 80 nm, at least 83 nm, at least 86 nm, at least 90 nm.
[0186] Embodiment 45. Abrasive grain according to any one of embodiments 1 and 82 to 84, wherein the coating comprises an average coating thickness of no greater than 150 nm, no greater than 140 nm, no greater than 130 nm, no greater than 120 nm, no greater than 110 nm, no greater than 100 nm.
[0187] Embodiment 46. Abrasive grain according to any one of embodiments 1 and 82 to 84, wherein the coating comprises an average thickness of not more than 200%, not more than 150%, not more than 100%, not more than 80%, not more than 50%, not more than 49%, not more than 47%, not more than 44%, not more than 42%, not more than 40%, not more than 38%, not more than 36%, not more than 34%, not more than 33%, not more than 31%, not more than 30%, not more than 29%, not more than 27%, not more than No greater than 25%, no greater than 23%, no greater than 21%, no greater than 20%, no greater than 19%, no greater than 18%, no greater than 17%, no greater than 16%, no greater than 14%, no greater than 12%, no greater than 11%, no greater than 10%, no greater than 9%, no greater than 8%, no greater than 7%, no greater than 6%, no greater than 5%, no greater than 4%, no greater than 3%, no greater than 2%, no greater than 1%, no greater than 0.8%, no greater than 0.7%, or no greater than 0.5% of the average thickness of the coating.
[0188] Embodiment 47. Abrasive grain according to any one of embodiments 1 and 82 to 84, wherein the coating comprises an average thickness of at least 0.001%, at least 0.05%, at least 0.08%, at least 0.1%, at least 0.2%, at least 0.3%, at least 0.4%, at least 0.5%, at least 0.7%, at least 0.8%, at least 0.9%, at least 1%, at least 1.2%, at least 1.5%, at least 1.8%, at least 2%, at least 2.2%, at least 2.5%, at least 2.8%, at least 3%, at least 4%, or at least 5% of the thickness standard deviation of the average thickness of the coating.
[0189] Embodiment 48. Abrasive grain according to any one of embodiments 1 and 82 to 84, wherein the coating comprises an amorphous phase content in the range of at least 90 wt % based on the total weight of the coating.
[0190] Embodiment 49. The abrasive grain of any one of Embodiments 1 and 82 to 84, wherein the coating consists essentially of an amorphous phase.
[0191] Embodiment 50. Abrasive grains according to any one of embodiments 1 and 82 to 84, further comprising a coating content of at least 0.01 wt.%, at least 0.02 wt.%, at least 0.03 wt.%, at least 0.04 wt.%, at least 0.05 wt.%, at least 0.06 wt.%, at least 0.07 wt.%, at least 0.08 wt.%, at least 0.09 wt.%, at least 0.1 wt.%, at least 0.15 wt.%, at least 0.16 wt.%, at least 0.17 wt.%, at least 0.18 wt.%, at least 0.19 wt.%, at least 0.2 wt.%, at least 0.25 wt.%, at least 0.26 wt.%, at least 0.27 wt.%, at least 0.28 wt.%, at least 0.29 wt.%, or at least 0.3 wt.%, based on the total weight of the core.
[0192] Embodiment 51. Abrasive particles according to any one of embodiments 1 and 82 to 84, further comprising a coating content of not more than 1 wt.%, not more than 0.9 wt.%, not more than 0.8 wt.%, not more than 0.7 wt.%, not more than 0.6 wt.%, not more than 0.55 wt.%, not more than 0.5 wt.%, not more than 0.48 wt.%, not more than 0.46 wt.%, not more than 0.45 wt.%, not more than 0.43 wt.%, not more than 0.42 wt.%, not more than 0.41 wt.%, not more than 0.4 wt.%, not more than 0.38 wt.%, not more than 0.37 wt.%, not more than 0.36 wt.%, not more than 0.35 wt.%, or not more than 0.34 wt.%, based on the total weight of the core.
[0193] Embodiment 52. Abrasive grains according to any one of embodiments 1 and 82 to 84, further comprising a ratio of average coating thickness to average particle size of the core, wherein the ratio is less than 1, not greater than 0.9, not greater than 0.7, not greater than 0.5, not greater than 0.4, not greater than 0.2, not greater than 0.1, not greater than 0.08, not greater than 0.06, not greater than 0.05, not greater than 0.03, not greater than 0.02, not greater than 0.01, not greater than 0.009, not greater than 0.008, not greater than 0.007, not greater than 0.006, not greater than 0.005, not greater than 0.004, not greater than 0.003, not greater than 0.002, or not greater than 0.1.
[0194] Embodiment 53. Abrasive grain according to any one of embodiments 1 and 82 to 84, further comprising a ratio of average coating thickness to average particle size of the core, wherein the ratio is at least 0.0005, at least 0.0007, at least 0.0009, at least 0.001, at least 0.002, at least 0.003, at least 0.004, at least 0.005, at least 0.006, at least 0.007, at least 0.008, at least 0.009, at least 0.01, at least 0.02, or at least 0.03.
[0195] Embodiment 54. The abrasive grain of any one of embodiments 1 and 82 to 84, wherein the coating further comprises at least one silane-containing composition.
[0196] Embodiment 55. Abrasive particles according to embodiment 54, wherein the coating comprises at least 0.02 wt%, or at least 0.5 wt%, or at least 1 wt%, or at least 2 wt%, or at least 3 wt%, or at least 4 wt%, or at least 5 wt%, or at least 6 wt%, or at least 7 wt%, or at least 8 wt%, or at least 9 wt%, or at least 10 wt% of the silane-containing composition, based on the total weight of the coating, or further wherein the coating comprises no more than 25 wt%, such as no more than 20 wt%, or no more than 18 wt%, or no more than 16 wt%, or no more than 14 wt%, or no more than 12 wt%, or no more than 10 wt% of the silane-containing compound, based on the total weight of the coating.
[0197] Embodiment 56. Abrasive particles according to any one of embodiments 1 and 82 to 84, wherein the abrasive particles have an average particle size of at least 10 microns, at least 30 microns, at least 40 microns, at least 50 microns, at least 60 microns, at least 70 microns, at least 80 microns, at least 90 microns, at least 100 microns, at least 120 microns, at least 140 microns, at least 150 microns, at least 170 microns, at least 180 microns, at least 200 microns, at least 210 microns, at least 230 microns, at least 250 microns, at least 260 microns, at least 270 microns, at least 290 microns, at least 300 microns, at least 320 microns, at least 340 microns, at least 350 microns, at least 360 microns, at least 380 microns, at least 400 microns, at least 420 microns, at least 430 microns, at least 440 microns, at least 450 microns, at least 460 microns, at least 470 microns, at least 490 microns, or at least 500 microns.
[0198] Embodiment 57. Abrasive particles according to any one of Embodiments 1 and 82 to 84, wherein the abrasive particles have an average particle size of not more than 3 mm, such as not more than 2 mm, not more than 1.8 mm, not more than 1.6 mm, not more than 1.5 mm, not more than 1.2 mm, not more than 1 mm, not more than 900 microns, not more than 850 microns, not more than 830 microns, not more than 800 microns, not more than 750 microns, not more than 700 microns, not more than 650 microns, not more than 600 microns, not more than 550 microns, not more than 500 microns, not more than 450 microns, or not more than 400 microns.
[0199] Embodiment 58. A fixed abrasive article comprising abrasive particles according to any one of embodiments 1 and 82 to 84.
[0200] Example 59. A fixed abrasive product according to Example 58, wherein the abrasive product has a moisturizing value of at least 70%, such as at least 71%, or at least 72%, or at least 73%, or at least 74%, or at least 75%, or at least 76%, or at least 77%, or at least 78%, or at least 79%, or at least 80%, or at least 81%, or at least 82%, or at least 83%, or at least 84%, or even at least 85%.
[0201] Embodiment 60. An abrasive grain batch comprising abrasive grains according to any one of embodiments 1 and 82 to 84.
[0202] Embodiment 61. A batch of abrasive particles according to Embodiment 60, wherein the batch comprises at least 10 wt%, or at least 20 wt%, or at least 30 wt%, or at least 40 wt%, or at least 50 wt%, or at least 60 wt%, or at least 70 wt%, or at least 80 wt%, or at least 90 wt% of the abrasive particles according to Embodiment 1, based on the total weight of the abrasive particles in the batch.
[0203] Embodiment 62. The batch of abrasive particles of Embodiment 60, wherein the batch consists essentially of abrasive particles of Embodiment 1.
[0204] Embodiment 63. The batch of abrasive particles according to Embodiment 60, wherein the abrasive particles include any one or more combinations of features of any one of the embodiments described in the Examples section or herein.
[0205] Embodiment 64. A method for forming an abrasive grain or a plurality of abrasive grains, comprising:
[0206] a) providing a core; and
[0207] b) forming a coating covering at least a portion of the core; wherein the coating comprises any one or more features of any of the Examples section or embodiments described herein.
[0208] Embodiment 65. A method according to Embodiment 64, wherein forming includes heating the coating at a temperature not greater than 800°C, or not greater than 700°C, or not greater than 600°C, or not greater than 500°C, or not greater than 400°C, or not greater than 300°C, or not greater than 250°C.
[0209] Embodiment 66. A method according to Embodiment 64, wherein forming includes heating the coating at a temperature of at least 20°C, or at least 30°C, or at least 40°C, or at least 50°C, or at least 60°C, or at least 70°C, or at least 80°C, or at least 90°C, or at least 100°C, or at least 110°C, or at least 120°C, or at least 130°C, or at least 140°C, or at least 150°C.
[0210] Embodiment 67. The method of Embodiment 64, further comprising providing a silane-containing material, a silanol-containing material, or a combination thereof overlying the coating.
[0211] Embodiment 68. The method of Embodiment 64, further comprising disposing the abrasive grain or grains in a fixed abrasive article.
[0212] Embodiment 69. The method of Embodiment 64, further comprising disposing the abrasive grain or grains in a bonded abrasive article.
[0213] Embodiment 70 The method of Embodiment 64, further comprising disposing the abrasive grain or grains in a fixed abrasive article comprising an organic bond material.
[0214] Embodiment 71. A method according to embodiment 70, wherein the organic bonding material comprises at least one of phenolic resin, epoxy resin, polyester, cyanate ester, shellac, polyurethane, polybenzoxazine, polybismaleimide, polyimide, rubber or a combination thereof.
[0215] Embodiment 72. An abrasive grain comprising:
[0216] A subject, the subject comprising:
[0217] core, and
[0218] a coating covering at least a portion of the core, wherein the coating comprises a total crystalline content of no greater than 60 vol % based on the total volume of the coating,
[0219] wherein the coating comprises at least one silicate-containing compound and at least one silica-containing compound; and
[0220] Wherein the coating comprises a silicate / silicon dioxide percentage of at least 10% and not more than 1000%.
[0221] Embodiment 73. Abrasive grains according to any one of Embodiments 72 and 82 to 84, wherein the coating comprises a total crystalline content of not more than 50 vol%, or not more than 40 vol%, or not more than 30 vol%, or not more than 20 vol%, or not more than 10 vol%, or not more than 8 vol%, or not more than 5 vol%, or not more than 3 vol%, or not more than 2 vol%, or not more than 1 vol%.
[0222] Embodiment 74 The abrasive grain of Embodiment 72, wherein the one silicate-containing compound comprises at least one of sodium silicate, potassium silicate, lithium silicate, or a combination thereof.
[0223] Embodiment 75. The abrasive grain of Embodiment 72 or 84, wherein the silica-containing compound comprises silica.
[0224] Embodiment 76. Abrasive grains according to any one of Embodiments 72 and 82 to 84, wherein the coating comprises a silica-containing compound content of at least 1 wt.%, at least 5 wt.%, or at least 10 wt.%, or at least 15 wt.%, or at least 20 wt.%, or at least 30 wt.%, or at least 40 wt.%, or at least 50 wt.%, or at least 60 wt.%, or at least 70 wt.%, or at least 80 wt.%, or at least 90 wt.%, based on the total weight of the coating.
[0225] Embodiment 77. Abrasive grains according to any one of Embodiments 72 and 82 to 84, wherein the coating comprises a silica-containing compound content of no more than 99 wt%, no more than 95 wt%, or no more than 90 wt%, or no more than 80 wt%, or no more than 70 wt%, or no more than 60 wt%, or no more than 50 wt%, or no more than 40 wt%, or no more than 30 wt%, or no more than 20 wt%, or no more than 10 wt%, based on the total weight of the coating.
[0226] Embodiment 78. Abrasive grains according to Embodiment 72, wherein the coating comprises a silicate compound content of at least 1 wt.%, at least 5 wt.%, or at least 10 wt.%, or at least 15 wt.%, or at least 20 wt.%, or at least 30 wt.%, or at least 40 wt.%, or at least 50 wt.%, or at least 60 wt.%, or at least 70 wt.%, or at least 80 wt.%, or at least 90 wt.%, based on the total weight of the coating.
[0227] Embodiment 79. Abrasive grains according to any one of Embodiments 72 and 82 to 84, wherein the coating comprises a silicate compound content of not more than 99 wt%, or not more than 95 wt%, or not more than 90 wt%, or not more than 80 wt%, or not more than 70 wt%, or not more than 60 wt%, or not more than 50 wt%, or not more than 40 wt%, or not more than 30 wt%, or not more than 20 wt%, or not more than 10 wt%, based on the total weight of the coating.
[0228] Embodiment 80. Abrasive grain according to embodiment 72 or 79, wherein the silicate / silicon dioxide percentage is at least 15%, or at least 20%, or at least 25%, or at least 30%, or at least 35%, or at least 40%, or at least 45%, at least 50%, or at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 100%.
[0229] Embodiment 81. Abrasive grains according to Embodiments 72 or 79, wherein the silicate / silicon dioxide percentage is no greater than 1000%, or no greater than 900%, or no greater than 800%, or no greater than 700%, or no greater than 600%, or no greater than 500%, or no greater than 400%, or no greater than 300%, 200%, or no greater than 190%, or no greater than 180%, or no greater than 170%, or no greater than 60%, or no greater than 150%, or no greater than 160%. 140%, or not more than 130%, or not more than 120%, or not more than 110%, or not more than 100%, or not more than 90%, or not more than 80%, or not more than 70%, or not more than 60%, or not more than 50%, or not more than 40%, or not more than 30%, or not more than 20%, or not more than 15%, or not more than 10%, or not more than 9%, or not more than 8%, or not more than 7%, or not more than 6%, or not more than 5%, or not more than 4%.
[0230] Embodiment 82. An abrasive grain comprising:
[0231] a core, the core comprising a ceramic material;
[0232] a coating comprising silicon and oxygen, the coating covering at least a portion of the core, wherein the coating comprises:
[0233] Nanoparticles;
[0234] Binder materials; and
[0235] Nanopore.
[0236] Embodiment 83. An abrasive grain comprising:
[0237] a core comprising a ceramic material including a magnetoplumbite crystalline phase; and
[0238] A coating covering at least a portion of the core, wherein the coating comprises:
[0239] Nanoparticles;
[0240] Binder materials; and
[0241] Nanopore.
[0242] Embodiment 84. The abrasive grain of Embodiment 82 or 23, wherein the nanoparticles comprise silica, and wherein the bond material comprises a silica-containing compound.
[0243] Examples
[0244] Example 1
[0245] A representative sample of abrasive particles was formed by first preparing a coating mixture comprising 7.01 grams of DS-13 silica available from Qingdao FUSO Co., Ltd. and 2.65 grams of Lithium Ion available from Dongguan Songshi Chemical Co., Ltd. A48 lithium silicate and 20.34 grams of deionized water. The proportions of the components in the mixture are 72 wt% colloidal silica solution and 28 wt% lithium silicate solution, which has the properties listed in Table 1. White Alumina 38A (white fused alumina (α-A 12 Aluminum oxide particles (03)>99%, 60grit) were used as core particles, and 1000.0 grams of molten aluminum oxide particles were mixed with 13.0 grams of coating mixture using a mixer for 1 to 5 minutes, and the core particles were coated with the coating mixture. The wet and coated abrasive particles were dried at 150° C. for 14 hours in a standard atmosphere to form coated abrasive particles (i.e., sample S1). The particles were not sintered and had a total crystal content of 0 vol% based on the total volume of the coating.
[0246] Table 1
[0247]
[0248] ICP Analysis Technique. The following is the ICP analysis technique used in this article to evaluate the composition of the coating, especially the inorganic materials in the coating. The coating of sample 1 was subjected to ICP analysis. The analysis results are listed in Table 3. Sample 1 has a lithium / silicon percentage of 2.9% and a sodium / silicon ratio of 5.9%. The analysis was performed as follows: First, 20.0 grams of sample S1 were weighed and 2 mL of hydrochloric acid, 0.5 mL of nitric acid, and 10 mL of hydrofluoric acid were added. The sample was then sealed in a digestion tank at 100°C for 1 hour. The sample was then filtered and the filtrate was measured by ICP-OES using the machine parameters provided in Table 2.
[0249] Table 2
[0250]
[0251] Table 3: ICP of coatings
[0252] composition wt% <![CDATA[Li2O]]> 2.69% <![CDATA[SiO2]]> 91.89% <![CDATA[Na2O]]> 5.42%
[0253] Example 2
[0254] A second representative example of coated particles, S2, was prepared following the same procedure as S1 of Example 1, except that the coating mixture of the abrasive particles was a 72 wt % colloidal silica solution and a 28 wt % potassium silicate solution, available from Xingtai Dayang Chemical Co., Ltd. as DY-4.0, having the properties listed in Table 4. The particles were unsintered and had a total crystalline content of 0 vol % based on the total volume of the coating.
[0255] Table 4
[0256]
[0257] ICP analysis was performed on the coating of S2. The analysis results are listed in Table 5. Sample 2 had a potassium / silicon percentage of about 3.2 to 7.7% and a sodium / silicon ratio of about 2.1% to 5.5%.
[0258] Table 5: ICP of coating S2
[0259] composition wt% <![CDATA[K2O]]> 3-7% <![CDATA[SiO2]]> 91-95% <![CDATA[Na2O]]> 2-5%
[0260] Example 3
[0261] A third representative example of coated particles, S3, was prepared following the same procedure as S1 of Example 1, except that the coating mixture of the abrasive particles was 80 wt % colloidal silica solution and 20 wt % sodium silicate solution, which was available from Xingtai Dayang Chemical Co., Ltd. as TPY-2.8, having the properties listed in Table 6. The particles were unsintered and had a total crystalline content of 0 vol % based on the total volume of the coating.
[0262] Table 6
[0263]
[0264] ICP analysis was performed on the coating of S3. The results of the analysis are listed in Table 7. Sample 3 had a sodium / silicon percentage of about 5.3 to 17.6%.
[0265] Table 7: ICP of coating S3
[0266] composition wt% <![CDATA[Na2O]]> 5-15% <![CDATA[SiO2]]> 85-95%
[0267] Example 4
[0268] Comparative coated particles CS1 were prepared by mixing white alumina 38A particles with DS-13 silica available from Qingdao Fuso Co., Ltd. at a silica content of 0.1 wt.% based on the total weight of the alumina particles for 3 to 5 minutes. A portion of the wetted particles were sintered at 850° C. for 15 minutes to form coated particle sample CS1 and had a total crystalline content of 63 vol% based on the total volume of the coating.
[0269] Example 5
[0270] A second comparative coated particle CS2 was prepared by mixing white aluminum oxide 38A particles with DS-13 silica available from Qingdao Fuso Co., Ltd. at a silica content of 0.1 wt.% based on the total weight of the aluminum oxide particles for 3 to 5 minutes. A portion of the wetted particles was dried at 150° C. for 14 hours to form a coated abrasive particle having a total crystal content of 0 vol% based on the total volume of the coating.
[0271] Example 6
[0272] The third comparative coated particle CS3 was prepared by first preparing a coating mixture comprising 2.88 g of DY-4.0 potassium silicate solution available from Xingtai Dayang Chemical Co., Ltd. and 10.38 g of Lithium available from Dongguan Songshi Chemical Co., Ltd. A48 lithium silicate and 16.74 grams of deionized water. The proportions of the components in the mixture are 78 wt% lithium silicate solution and 22 wt% potassium silicate solution, which has the properties listed in Table 8. White Alumina 38A (white fused alumina (α-A 12 Abrasive particles (S) (03)) were used as core particles, and 1000.0 grams of fused alumina particles were mixed with 13.0 grams of a coating mixture using a mixer for 1 to 5 minutes to coat the core particles with the coating mixture. The wet and coated abrasive particles were dried at 150° C. for 14 hours to form coated abrasive particles (i.e., sample CS3). The particles were not sintered and had a total crystal content of 0 vol% based on the total volume of the coating.
[0273] Table 8
[0274] composition Chemical composition of the coating mixture Ratio Potassium silicate solution <![CDATA[K2O·nSiO2 (n = 4.0) in water; (20% SiO2 concentration)]]> 22wt% Lithium silicate solution <![CDATA[Li2O·nSiO2 (n = 4.8) in water; (20% SiO2 concentration)]]> 78wt%
[0275] Example 7
[0276] A fourth comparative coated particle CS4 was prepared by first preparing a coating mixture comprising 8.76 grams of TPY-2.8 sodium silicate solution available from Xingtai Dayang Chemical Co., Ltd. and 21.24 grams of deionized water. The components in the mixture were 100 wt % sodium silicate having the properties listed in Table 9. White Alumina 38A (white fused alumina (α-A12 Abrasive particles (03)) were used as core particles, and 1000.0 grams of fused alumina particles were mixed with 13.0 grams of a coating mixture using a mixer for 1 to 5 minutes to coat the core particles with the coating mixture. The wet and coated abrasive particles were dried at 150°C for 14 hours to form coated abrasive particles (i.e., sample CS4). The particles were not sintered and had a total crystal content of 0 vol% based on the total volume of the coating. The particles of CS4 could not be used due to significant agglomeration of the particles, which is believed to be due to the coating components. See Figure 7 Agglomeration of particles.
[0277] Table 9
[0278]
[0279] Example 8
[0280] A fifth comparative coated particle CS5 was prepared by first preparing a coating mixture comprising 13.27 g of DY-4.0 potassium silicate solution available from Xingtai Dayang Chemical Co., Ltd. and 16.73 g of deionized water. The components in the mixture were 100 wt % potassium silicate having the properties listed in Table 10. White Alumina 38A (white fused alumina (α-A l2 Abrasive particles (03)) were used as core particles, and 1000.0 grams of molten alumina particles were mixed with 13.0 grams of a coating mixture using a mixer for 1 to 5 minutes to coat the core particles with the coating mixture. The wet and coated abrasive particles were dried at 150° C. for 14 hours to form coated abrasive particles (i.e., sample CS5). The particles were not sintered and had a total crystal content of 0 vol% based on the total volume of the coating.
[0281] Table 10
[0282] composition Chemical composition of the coating mixture Ratio Potassium silicate solution <![CDATA[K2O·nSiO2 (n = 4.0) in water; (20% SiO2 concentration)]]> 100wt%
[0283] Example 9
[0284] The coated alumina particles of samples S1, S2, S3, CS1, CS2, CS3, CS4, and CS5 were further treated with 3-aminopropyltriethoxysilane and dried at 150°C for 14 hours to form abrasive particles.
[0285] Example 10
[0286] The coated aluminum oxide particles of Use Example 3 were used with their corresponding abrasive particle samples to form grinding wheel S1, grinding wheel S2, grinding wheel S3, grinding wheel CS1, grinding wheel CS2, and grinding wheel CS4, respectively.
[0287] Grinding wheel S1 was prepared by mixing 74.3 grams of sample S1 abrasive grains with a bonding mixture containing phenolic resin for 2 to 7 minutes until all sample S1 abrasive grains were coated with the bonding mixture to form an abrasive mixture. The abrasive mixture was then molded and cold pressed to the desired size under a 300-ton press at room temperature to form a green grinding wheel. The green grinding wheel was removed from the mold and heat-treated in an oven at 160° C. for 15 hours.
[0288] All other grinding wheels (including grinding wheel S2, grinding wheel S3, grinding wheel CS1, grinding wheel CS2, and grinding wheel CS4) are formed using the same bonding mixture composition as grinding wheel S1 and are prepared according to the same process as grinding wheel S1, except that each grinding wheel uses the corresponding abrasive particles listed above (i.e., grinding wheel S2 contains S2 particles instead of S1 abrasive particles, grinding wheel S3 contains S3 abrasive particles instead of S1 abrasive particles, etc.). All grinding wheels are formed to have the same grinding wheel structure as grinding wheel S1, including porosity content, abrasive particle content, and bonding mixture content.
[0289] All wheels were tested for wet and dry flexural strength (i.e., MoR). To measure the wet MOR, the samples were soaked in boiling water for 2.5 hours before measurement. Table 11 summarizes the dry and wet MoR. Moisture retention is measured by dividing the wet MOR by the dry MOR and multiplying by 100. MOR is measured according to the published three-point bend test.
[0290] Table 11
[0291]
[0292] Surprisingly, it was noted that the grinding wheels with dry coatings (i.e., S2, S2, and S3) were statistically equivalent in their performance when compared to grinding wheel CS1 comprising abrasive grains with sintered coatings. Abrasive grains prepared by cryogenic processes may have benefits in terms of both sustainability and manufacturing.
[0293] Example 11
[0294] Another representative sample S11 of abrasive particles was formed as follows. Abrasive particles CG-2 were coated with the coating mixture mentioned in Table 1 in the same manner as described in Example 1. The coated particles were further treated with 3-aminopropyltriethoxysilane and dried at 150° C. for 14 hours to form abrasive particles S11. The properties and compositions of the CG-1 particles and CG-2 particles are described in Table 12.
[0295] Table 12
[0296]
[0297]
[0298] He density can be measured using a hydrometer AccuPyc II 1340 or equivalent as follows: Use an analytical balance with a readability of 0.1 mg or 0.0001 g to weigh a specific amount of sample, which can be filled with a 10 cm 3 Sample cup with more than 75% volume of nominal volume; closed lid for absolute density testing.
[0299] LPD / bulk density can be measured using a conventional microparticle bulk density tester, model DMP-II from ZSSM or equivalent, according to GB / T 20316.1-2009.
[0300] As disclosed in Table 12, CG-2 microparticles exhibit lower hardness and increased toughness compared to CG-1 microparticles.
[0301] Grinding wheel samples S12 to S14 and CS15 to CS19 were made using their respective mixtures containing abrasive grains and the same binder material (i.e., phenolic resin). The abrasive mixtures were molded and cold pressed at room temperature under a 300-ton press to form green bodies, which were then removed from the molds and cured at 160° C. for 15 hours. Samples S12 to S14 were prepared using blends of abrasive grains, including those of sample S11. All abrasive grains were 36 grit.
[0302] Sample S12 contained 46 volume % abrasive grains (11 volume % S11 grains, 26 volume % single crystal aluminum oxide particles, 9 volume % green silicon carbide particles), 19 volume % bond material, and 35 volume % porosity based on the total volume of the grinding wheel body.
[0303] Sample S13 contained 46 volume % abrasive grains (19 volume % S11 grains, 18 volume % single crystal aluminum oxide particles, 9 volume % green silicon carbide particles), 19 volume % bond material, and 35 volume % porosity based on the total volume of the grinding wheel body.
[0304] Sample S14 contained 46 volume % abrasive grains (26 volume % S11 grains, 11 volume % single crystal aluminum oxide particles, 9 volume % green silicon carbide particles), 19 volume % bond material, and 35 volume % porosity based on the total volume of the grinding wheel body.
[0305] Samples CS15, CS16 and CS17 (uncoated) were prepared with CG-2 particles. Sample CS15 contained 46% abrasive particles (11% CG-2 particles, 26% single crystal alumina particles, 9% green silicon carbide particles), 19% bond material and 35% porosity by volume, based on the total volume of the grinding wheel body.
[0306] Sample CS16 (5 Whitecut AG 36G B37) contains 46 volume % abrasive particles (19 volume % CG-2 particles, 18 volume % single crystal alumina particles, 9 volume % green silicon particles), 19 volume % bond material, and 35 volume % porosity, based on the total volume of the grinding wheel body.
[0307] Sample CS17 comprises 46 volume % abrasive particles (26 volume % CG-2 particles, 11 volume % single crystal alumina particles, 9 volume % green silicon carbide particles), 19 volume % binder material (comprising phenolic resin), and 35 volume % porosity, based on the total volume of the grinding wheel body.
[0308] Samples CS18 and CS19 were prepared using CG-1 particles. All abrasive particles were 36 grit. Sample CS18 contained 46 volume % abrasive grains (11 volume % CG-1 particles, 26 volume % single crystal alumina particles, 9 volume % green silicon carbide particles), 19 volume % binder material, and 35 volume % porosity.
[0309] Sample CS19 contains 46 volume % abrasive particles (19 volume % CG-1 particles, 18 volume % single crystal alumina particles, 9 volume % green silicon carbide particles), 19 volume % binder material (including phenolic resin) and 35 volume % porosity, accounting for the total volume of the grinding wheel body.
[0310] The modulus of rupture (MOR) was tested on strip samples cut from grinding wheel samples S12 to S14 and CS15 to CS19 under dry and wet conditions. The MOR was tested according to the embodiments of the present invention. A group of strip samples were soaked in boiling water for 2.5 hours and then tested for MOR. The results were used as the wet MOR. The MOR tested on another group of strip samples that were not soaked was used as the dry MOR. The moisture retention of the strip samples was determined by the following formula: Moisture Retention = (Dry MOR / Wet MOR) × 100, and is included in the following Table 13. Compared with samples CS15-CS19, samples S12, S13 and S14 showed improved moisture retention.
[0311] Grinding tests were conducted on grinding wheel samples S12 to S14 and CS15 to CS19 using M2 steel as the workpiece. 3The G-ratios of the grinding wheel samples at an MRR of 0.1% / s / mm are included in Table 13 below. Samples CS16 and CS17 show similar G-ratios despite different contents of abrasive particles and perform slightly better than CS15 (G-ratio increased by about 6%). It should be understood that a higher G-ratio indicates better performance. Samples CS16 and CS17 have a higher content of abrasive particles than sample CS18, but show a G-ratio similar to sample CS18. Sample CS19 shows a higher G-ratio compared to samples CS15 to CS18. Samples S12 and CS15 have similar contents of abrasive particles, but sample S12 shows an improved G-ratio compared to CS15. Samples S13 and CS19 show similar G-ratios, while sample 14 shows a higher G-ratio compared to sample CS19.
[0312] Table 13
[0313]
[0314] Fig. 8A A scanning electron microscope (SEM) image of a portion of an NQ particle 810 including α-alumina crystallites 811 is included. Figure 8B Included is an SEM image of a portion of a Whitecut particle 820, which includes a primary crystalline phase 822 and a secondary magnetoplumbite crystalline phase 821. The primary crystalline phase 822 includes α-alumina crystallites. The secondary phase 821 includes a rare earth aluminate.
[0315] Fig. 9 A graph of material removal rate (MRR) versus G-ratio for grinding wheel samples S12 to S14 and CS15 to CS19 is included. As shown, for a given material removal rate, grinding wheel sample S14 exhibits a higher G-ratio than grinding wheel samples S12, S13, and CS16 to CS19. Sample S13 exhibits a similar G-ratio to CS19 at the material removal rate tested and a higher G-ratio than samples S12 and CS15 to CS18. Sample S12 exhibits an improved G-ratio compared to samples CS15 to CS18.
[0316] Example 12
[0317] Abrasive grain samples CS20 to CS22 were formed using 36 grit of white aluminum oxide 38A particles. Abrasive grain sample S24 was formed using 36 grit of CQ-2 particles.
[0318] Sample CS20 was formed by mixing 1000.0 grams of abrasive grains with 13.0 grams of the formulation in Table 14 using a mixer. The wetted abrasive grains were sintered at 850° C. for 15 minutes to form coated microparticles, which were further treated with 3-aminopropyltriethoxysilane and dried at 150° C. for 14 hours to form coated abrasive grains of sample CS20.
[0319] Table 14
[0320]
[0321] Sample CS21 was formed by mixing 1000.0 grams of abrasive grains with 13.0 grams of the formulation of Table 15 using a mixer. The wetted abrasive grains were dried at 150° C. in air for 14 hours to form coated microparticles, which were further treated with 3-aminopropyltriethoxysilane and dried at 150° C. for 14 hours to form coated abrasive grains of sample CS21.
[0322] Table 15
[0323] composition Chemicals in coating mixtures preparation Lithium silicate solution <![CDATA[Li2O·nSiO2 (n = 4.8); concentrated 20% SiO2]]> 44 g DI water <![CDATA[H2O]]> 56 g
[0324] Sample CS22 was formed by mixing 1000.0 grams of abrasive grains with 13.0 grams of the formulation of Table 14 using a mixer. The wetted abrasive grains were sintered at 850° C. for 15 minutes to form coated microparticles, which were further treated with 3-aminopropyltriethoxysilane and dried at 150° C. for 14 hours to form coated abrasive grains of sample CS22.
[0325] Sample CS23 was formed by mixing 1000.0 grams of abrasive grains with 13.0 grams of the formulation of Table 13 using a mixer. The wet and coated abrasive grains were dried at 150° C. in air for 14 hours to form coated microparticles, which were further treated with 3-aminopropyltriethoxysilane and dried at 150° C. for 14 hours to form coated abrasive grains of sample CS23.
[0326] Sample S24 was formed by first treating the CQ-2 microparticles in the same manner as described for Sample S 1. The coated microparticles were further treated with 3-aminopropyltriethoxysilane and dried at 150°C for 14 hours to form the coated abrasive grains of Sample S24.
[0327] Fig. 10A Included is a SEM image showing a portion of the coating of sample S11010 at 50,000X magnification. Fig. 10B include Fig. 10AA further enlarged view (100,000X magnification) of the boxed area 1011 of FIG. 100. As shown, the coating 1010 includes nanopores 1012 and appears relatively rough.
[0328] Fig. 10C Included is a SEM image showing a portion of the coating of sample CS201020 at 50,000X magnification. Fig. 10D include Fig. 10C A further enlarged view (100,000X magnification) of the boxed area 1021 of FIG. 1020 is shown. As shown, the coating 1020 appears relatively smooth and Fig. 10A The coating 1010 is smoother. No nanopores were observed in the selected area of about 1.5 μm×0.75 μm.
[0329] Fig.10E Included is a SEM image showing a portion of the coating of sample CS211030 at 50,000X magnification. Fig.10F include Fig.10E A further magnified view (100,000X magnification) of the boxed area 1031 of FIG. 1030 is shown. As shown, the coating 1030 appears relatively rough. No nanopores are observed within the selected area of approximately 1.5 μm×0.75 μm.
[0330] Figure 10G Included is a SEM image showing a portion of the coating of sample CS221040 at 50,000X magnification. Fig. 10H include Figure 10G A further enlarged view (100,000X magnification) of the boxed area 1041 of FIG. 1041 is shown. As shown, the coating 1030 appears relatively smooth and Figure 10G The coating 1010 is smoother. No nanopores were observed in the selected area of about 1.5 μm×0.75 μm.
[0331] Fig.11A Included is a SEM image showing a portion of the coating of sample CS231110 at 100,000X magnification. Fig. 11B include Fig.11A 11. A further enlarged view (200,000X magnification) of the boxed area 1111 of FIG. 11. As shown, the coating 1110 includes discrete silica nanoparticles 1112.
[0332] Fig. 11C Included is a SEM image showing a portion of the coating of sample S241120 at 100,000X magnification. Fig.11D include Fig. 11C1121 of the frame area 1120. As shown, the coating 1120 includes nanopores 1122 and agglomerated nanoparticles 1123, which include silicate binders and silica nanoparticles. Compared with CS23, the coating 1120 includes fewer discrete nanoparticles. The above embodiments represent differences from the prior art. The embodiments relate to abrasive particles, which include a coating covering a core. In particular, the abrasive particles can include a thin conformal coating with improved average thickness and uniformity, which can promote the improvement of the performance of the abrasive particles in the fixed abrasive, such as reducing friction, anti-aging, and chemical and mechanical bonding of the conformal layer to the surface of the abrasive particles (i.e., the core particles) in relation to their use in material removal operations. In addition, the abrasive particles can have improved bonding strength and reduced hygroscopicity and / or permeability, and are particularly suitable for use in coated abrasives and thin wheels.
[0333] Compared with the abrasive article containing the abrasive grain with dry coating, the abrasive article formed with the representative abrasive grain further shows improved performance and properties, such as wet MoR, grinding ratio and MMR. Without wishing to be bound by any theory, the improved properties and performance of the abrasive article can be promoted by one or more characteristics of the abrasive grain.
[0334] The benefits, other advantages and solutions to the problems have been described above with reference to specific embodiments. However, the benefits, advantages, solutions to the problems and any features that may make any benefit, advantage or solution conceivable or more significant are not considered to be key, required or necessary features of any or all claims. The materials mentioned herein including one or more components may be interpreted as including at least one embodiment in which the material is substantially composed of the specified one or more components. The term "substantially composed of..." should be interpreted as including ingredients that include those materials specified and exclude all other materials except for a small amount of materials (e.g., impurity content) that do not significantly change the properties of the material. In addition or alternatively, in certain non-limiting embodiments, any of the compositions specified herein may be substantially free of materials that are not explicitly disclosed. The embodiments herein include ranges of certain component contents within the material, and it should be understood that the component contents within a given material total 100%.
[0335] The description and illustration of the embodiments described herein are intended to provide a general understanding of the structure of various embodiments. The description and illustration are not intended to be used as a detailed and comprehensive description of all elements and features of the device and system using the structure or method described herein. A separate embodiment may also be provided in a combined manner in a single embodiment, and conversely, the various features described in the context of a single embodiment for simplicity may also be provided individually or in any sub-combination. Further, references to values represented by ranges include each value and all values within the range. Only after reading this specification, many other embodiments will be apparent to the technician. Other embodiments may be utilized and obtained by the present disclosure, so that structural replacement, logical replacement or other changes may be performed without departing from the scope of the present disclosure. Therefore, the present disclosure should be considered illustrative and not restrictive.
Claims
1. An abrasive particle comprising: A subject, the subject comprising: core, and A coating covering at least a portion of the core, wherein the coating comprises at least one of the following: a.) a lithium / silicon percentage in a range of at least 0.01% to no more than 25%; b.) a potassium / silicon percentage in the range of at least 0.01% to no more than 40%; c.) a sodium / silicon percentage in the range of at least 0.01% to no more than 40%; or d) any combination thereof. 2 . The abrasive grain of claim 1 , wherein the lithium comprises lithium oxide.
3. The abrasive grain of claim 1, wherein the silicon comprises silicon dioxide. The abrasive grain of claim 1 , wherein the potassium comprises potassium oxide.
5. The abrasive grain of claim 1, wherein the sodium comprises sodium oxide.
6. The abrasive particle of claim 1, wherein the coating comprises a total crystalline content of no greater than 1 vol% based on the total volume of the coating.
7. An abrasive particle comprising: A subject, the subject comprising: core, and a coating covering at least a portion of the core, wherein the coating comprises a total crystalline content of no greater than 60 vol % based on the total volume of the coating, wherein the coating comprises at least one silicate-containing compound and at least one silica-containing compound; and Wherein the coating comprises a silicate / silicon dioxide percentage of at least 10% and not more than 1000%.
8. An abrasive particle comprising: a core, the core comprising a ceramic material; a coating comprising silicon and oxygen, the coating covering at least a portion of the core, wherein the coating comprises: Nanoparticles; Binder materials; and Nanopore.
9. An abrasive particle comprising: a core comprising a ceramic material including a magnetoplumbite crystalline phase; and A coating covering at least a portion of the core, wherein the coating comprises: Nanoparticles; Binder materials; and Nanopore.
10. Abrasive particles according to claim 8 or 9, wherein the nanoparticles comprise silica, and wherein the bond material comprises a silica-containing compound.
Citation Information
Patent Citations
Abrasive article including shaped abrasive particles
US20150291865A1
Abrasive article including shaped abrasive particles
US20150291866A1
Abrasive article including shaped abrasive particles
US20150291867A1
